Upregulation of YAP attenuates doxorubicin-induced cardiotoxicity through inhibiting ferroptosis - Yuming Zhang; Anbo Zhao; Li Tang; Shicheng Xia; Rui Wang; Qin Gao; Hongwei Ye (Tissue and Cell, 2027)

Unraveling the mechanism of gluten protein restructuring in modulating the cracking behavior of dumpling wrappers during freeze-thaw cycles - Li-Qin Tang; Xiaohong Sun; Xiao-Na Guo; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Short-chain chitosan quaternary ammonium salt-grafted PAO fibers with synergistic adsorption mechanism for efficient uranium extraction from seawater - Wentong Liu; Haonan Qin; Qiang Xian; Xingrui Tang; Shibing Zuo; Bo Yang; Dehong Liu; Wenmeng Wu; Changqiong Xie; Hao Li; Jun Wen; Lili Liu; et al. (Desalination, 2026)

An uncertainty-guided and knowledge-informed inversion framework for spatial-temporal numerical modeling of rockfill dams - Qin Ke; Dian-Qing Li; Xiao-Song Tang (Computers and Geotechnics, 2026)

Insights into the functions of MYB29 and MYB28.1 involved in glucosinolate biosynthesis from Isatis indigotica Fort. - Yan Zhang; Zhaojin Xu; Kaiwei Qin; Jiamin Kang; Limi Tang; Bowen Duan; Zhihua Liu; Tao Li (Functional & Integrative Genomics, 2026)

Combining zircon age, Hf-O isotopes and amphibole composition to assess the Cu-Ni-Co mineralization potential in East Tianshan mafic-ultramafic intrusions - Kezhang Qin; Dongmei Tang; Chao Li; Noreen J. Evans; Wenlong Xie; Junjie Yang (Lithos, 2026)

lnc5714 participates in silkworm resistance to Nosema bombycis infection by regulating MRPL4-related host energy metabolism - Li Sui; Qiong Yu; Wangbin Qin; Yujia Fang; Pingyang Wang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

Calcium isotopes constrain magmatic–hydrothermal evolution and Nb–REE decoupling in the Bayan Obo carbonatite system - Zhuoming Li; Qingyan Tang; Chi Zhao; Hailong Jin; Shang Liu; Jiaolong Zhao; Biao Chen; Yanjiang Liu; Yan Zhang; Tianyu Qin; Min Qiao; Xinrui Bai; et al. (Gondwana Research, 2026)

Integrated electronic nose, GC–MS, and metagenomic analyses reveal volatile flavor and microbial community differences in heap-fermented grains of Jiangxiangxing Baijiu across different fermentation degrees - Guiyin Li; Lixia Shen; Lei Nie; Ping Tang; Qimuge Shan; Liqin Qin; Shuangxi Fan; Xuewu Guo (Food Research International, 2026)

Constructing antimicrobial oil-in-water emulsions via spatially diffused ionic interlocking networks between chlorhexidine digluconate and polysaccharides - Xin Tang; Yidan Zhang; Mei Li; Qiujun Yu; Jisheng Yang; Jin Wang; Ningjing Sun; Jialong Wen; Zhiyong Qin (Food Research International, 2026)

Unraveling the aroma-producing mechanism of the xerophilic fungus Xerochrysium coryli via integrated transcriptomic and volatile metabolomic analysis - Zengye Yang; Weili Yang; Zhengchuan He; Jin Zhou; Chongde Wu; Yizhi Tang; Ruina Zhang; Jiayi Li; Yuhang Zou; Mingyue Zhang; Yanqing Qin; Yao Jin (Fungal Biology, 2026)

Impact of barrier lake collapse on hydrological characteristics and fish habitats: A case study in the Qinghai-Tibetan Plateau - Yunong Qin; Qi Tang; Yuanming Wang; Kefeng Li; Ruifeng Liang (Ecological Modelling, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Viral persistence and host-state remodeling in virus-associated cancers - Jiaqi Ma; Jianchao Guo; Guohao Li; Xinliang Liu; Qin Tang; Zhong Luo; Jinxin Sun; Zhiwei Guo; Xueqin Yan; Xiangxiang Xu (Archives of Microbiology, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

Distinct impacts of ferric iron and sulfate on anaerobic microbial dechlorination of polychlorinated biphenyls (PCBs): insights from congener-specific and microbial community analyses - Yanqiang Tang; Xuexin Han; Ying Wang; Yang Li; Qingdong Qin; Yan Xu (Environmental Research, 2026)

Defect-engineered CuO nanosheets promote asymmetric *CO-*CHO coupling for ampere-level CO2-to-C2+ electroreduction - Lei Pan; Yaxin Jin; Siyu Tang; Zhanpeng Liang; Yihan Xu; Jianlong Lin; Jie Li; Yuyi Qin; Xinyun Hu; Yuanyuan Xu; Jiahao Zhou; Wei Wang; et al. (Chemical Engineering Journal, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Product-grade enrichment of byproduct deuterium in PEM natural water electrolysis for hydrogen production - Zezheng Zhang; Jinguang Cai; Chao Lv; Ning Zeng; Aojie Liu; Qin Li; Liuxin Yang; Rui Hou; Siyi Liu; Peilong Li; Yan Shi; Xiaopeng Wang; et al. (Journal of Cleaner Production, 2026)

Elevated water levels drive greenhouse gas mitigation in the riparian zone profile - Qingbang Du; Ruiliang Xu; Yu Qin; Xinchen Cai; Chunhui Zhan; Ziman Song; Longbin Yu; Zhaowen Wang; Chenyu Li; Ziyang Tang; Yifei Li; Shanyun Wang; et al. (Journal of Environmental Management, 2026)

Microbial sulfur metabolism affects methane oxidation efficiency of anaerobic methane oxidation in different medium environments - Xunsen Chen; Peng Huang; Wenwen Huang; Zhenzhen Peng; Shubing Li; Yi Tang; Mengchen Lu; Teng Guo; Fangrong Wei; Jinshao Ye; Huaming Qin; Yan Long (International Biodeterioration & Biodegradation, 2026)

The TLR9/NF-κB and cGAS/STING pathways mediate​ the assembly of the NLRP3 inflammasome induced by Singapore grouper iridovirus DNA - Lifang Cao; Lu Yang; Runjian Huang; Dekun Tang; Zihan Li; Yunxiang Jiang; Min Yang; Qiwei Qin; Shina Wei (Fish & Shellfish Immunology, 2026)

Atomic-level regulation of peroxymonosulfate activation on coal gangue: Toward controllable catalytic pathways and enhanced environmental resilience - Lixin Li; Peijiang Han; Tao Qin; Bo Zhang; Linlin Huang; Xue Dong; Qingju Tang; Xin Zhao; Fengxia Deng (Environmental Research, 2026)

Chronic paracetamol exposure disrupts behavior and induces intrinsic apoptosis in a freshwater bivalve - Yun-xia Hou; Shi-yin Tang; Wang Liu; Zhi-tong Li; Kai-jian Wei; Xiang-sheng Hong; Jian-hui Qin; Jin-miao Zha (Environmental Pollution, 2026)

Carbon aerogels for water treatment: Frontiers and challenges in scale-up and application - Chunyan Yang; Jiawang Qin; Yi Deng; Quanxun Liang; Shun Tang; Jialin Shi; Lu Yang; Xin Yang; Zhaoying Li; Jiale Wang; Wenjie Wang; Jun Ma; et al. (Desalination, 2026)

Hydrologic and sediment responses to vegetation changes from Eagleson's ecohydrological perspective - Zhiqiang Tang; Qiang Liu; Liqiao Liang; Jifa Qin; Jianfei Wu; Yuting Yang; Xuan Wang; Chunhui Li (CATENA, 2026)

R2R3-MYB transcription factor MYB113 specifically regulates anthocyanin accumulation in Lycium ruthenicum - Tingting Li; Zihan Zhang; Jingjin Wang; Huan Qin; Lin Tang (Plant Cell Reports, 2026)

Multi-component microneedle drug delivery system of sanfu herbal patch for allergic asthma in rats - Ying Lv; Xiaoshuang Li; Yu Wang; Xinxin Qin; Ye Tang; Meng Li; Yufei Feng (Drug Delivery and Translational Research, 2026)

Enhancing large-scale streamflow prediction by coupling structural inductive bias with meta-learning - Xuan Tang; Yuting Zhao; Yuan Yu; MingRui Yu; Guanghua Qin; Hongxia Li (Journal of Hydrology, 2026)

The extract of Cirsium setosum exerts antimicrobial activities on largemouth bass infected by Aeromonas veronii via regulating inflammatory and antioxidant responses - Yuhuan Qiu; Chutong Zhang; Dekun Tang; Dasen Li; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Magnetic-field-driven TENG-EMG hybrid energy harvester for self-powered sensing in power equipment - Song Xiao; Boyang Li; Jingzi Qin; Xiaoxing Zhang; Ju Tang; Yi Li (Chemical Engineering Journal, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Improved photovoltaic performance via synergistically combining electric poling and flexoelectricity on lead-free ferroelectric (KNbO3)0.9(BaNi1/2Nb1/2O3-δ)0.1 films - Chuanqing Li; Yu Cai; Feifan Hu; Zhihua Duan; Tao Wang; Xiaomei Qin; Yanxue Tang; Xiangyong Zhao; Aiyun Liu; Feifei Wang; Zhongchen Gao; Fang Wang; et al. (Chemical Engineering Journal, 2026)

Two Fatty Acids From Host Plant Leaves Are Attractive to Soritia leptatina Adults - Qianwen Ma; Qin Li; Tingting Tan; Yifei Meng; Hongquan Wang; Yiqu Chen; Xiaoqin Tang (Journal of Chemical Ecology, 2026)

Performance evaluation of a dual-core heating R290 heat pump system based on RSM and NSGA-II - Yinghui Miao; Ming Li; Xuebin Li; Jun Wang; Zhuren Qin; Xingwang Tang (International Journal of Refrigeration, 2026)

Wind and buoyancy controls on productivity and bottom current in the Pacific Antarctic seasonal sea-ice zone since 300 ka - Jiakai Wang; Jingteng Guo; Wenshen Xiao; Zheng Tang; Bingbin Qin; Jörg Lippold; Zhifang Xiong; Tiegang Li (Global and Planetary Change, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Liver transplantation promotes early neural reorganization in minimal hepatic encephalopathy: a longitudinal resting state fMRI study - Yunli Zhang; Xiaogang Tang; Bin Qin; Shiting Tang; Yan Li; Zhai Huang; Zhijian Liang (Metabolic Brain Disease, 2026)

Rating chaos and green governance: ESG rating divergence, corporate greenwashing, and the governance effects of environmental tax reform - Ke Li; Tian Qin; Liwei Tang; Jieming Zhou (Environment, Development and Sustainability, 2026)

Genome Analysis and Reproductive Observations Suggest Allotetraploidy and a Potential Reproduction–Metabolism Association in the Endangered Fish Neolissochilus heterostomus - Tiaoyi Xiao; Zhichao Wu; Dongfang Li; Beibei Qin; Shengguo Tang; Chengyi Lin; Kuayun Mao; Jinwu Yin; Zhihu Li; Hongquan Wang; Zhao Lv (Fishes, 2026)
Neolissochilus heterostomus, a cyprinid fish endemic to Yunnan Province, China, is highly valued for both ornamental and edible purposes, yet its wild populations are currently declining and classified as endangered. In this study, we present a chromosome-level genome assembly of N. heterostomus, utilizing the PacBio HiFi and Hi-C strategies. The assembled genome spans 1793.99 Mb and is anchored to 50 chromosomes, comprising a total of 50,203 genes. Genomic features and chromosomal karyotype data recorded in the present study are consistent with an allotetraploid origin for N. heterostomus. Comparative genomics shows that N. heterostomus shares a close phylogenetic relationship with another allotetraploid fish, the common carp Cyprinus carpio. In total, 4687 expanded and 1365 contracted gene families were identified in N. heterostomus. Further enrichment analyses indicated an overrepresentation of metabolism-related pathways among the expanded and positively selected gene families, whereas the contracted gene families were enriched in reproduction- and embryonic development-related pathways. Reproductive observations further indicate that N. heterostomus produces fewer eggs than other cyprinid species characterized by relatively long embryonic development periods (106.1 h; accumulated temperature: 2260.6 °C·h), including common carp, goldfish (Carassius auratus), grass carp (Ctenopharyngodon idella), pond loach (Misgurnus anguillicaudatus), and blunt snout bream (Megalobrama amblycephala). These findings suggest a potential association between metabolism-related genomic features and reproductive traits, although functional validation remains necessary. Overall, this study may offer insights into the polyploidization, metabolic, and reproductive traits of N. heterostomus, thereby providing genomic and biological resources that may support future studies relevant to the conservation and management of this endangered species.

Water-quality responses and management-oriented spatial thresholds in a complex river-estuary continuum - Jiang Wu; Tang Liu; Dian-Bao Li; Li-Juan Zhang; Hua-Peng Qin; Wei-Ling Sun; Nan Xu (Water Research, 2026)

Study on the mechanism of DLK1 in placenta of intrahepatic cholestasis of pregnancy - Zhizun Li; Xiaomei Huang; Yong Shao; Qin Tang (Tissue and Cell, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Process design and optimization for resource-efficient recovery of Fe, P, and Ti from a low-grade complex iron ore - Shiteng Qin; Xiaokun Li; Bing Zhao; Peng Gao; Yanjun Li; Zhidong Tang (Minerals Engineering, 2026)

Mechanism elucidation for electrochemical simultaneous detection of multiple electron-rich phytohormones on a portable flexible sensor and virtual visualization - Shiyu Hu; Xiaoli Wang; Fengwei Li; Shumo Zhou; Xiyi Tang; Yi Peng; Le Wu; Qinyi Cao; Shiyi Xia; Yahui Huang; Songbai Zhang; Jifei Yang; et al. (Journal of Hazardous Materials, 2026)

Atmospheric reaction molecular network suggests transformation-driven chemodiversity of secondary organic aerosols - Feifei Li; Jitao Lv; Shanshan Tang; Qiurui Zhang; Yiru Qin; Qiying Nong; Xianwei Wang; Yongshun Huang; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2026)

Temperature-induced pupal pigmentation in Antheraea pernyi is affected by ApADC through the regulation of NBAD biosynthesis - Qi Wang; Jingwen Tang; Yunmin Jiang; Xueying Jiang; Yong Wang; Wei Liu; Li Qin (Insect Biochemistry and Molecular Biology, 2026)

Smart autologous plasma-ICG self-assembled carriers prolong half-life of growth factors and enhance antibacterial effect for periodontitis therapy - Hailun Zhou; Jun Zhou; Xiaoqi Wang; Li Tang; Cong Liu; Chunyun Liang; Hejia Qin; Shufang Zhuo; Ao Long; Fengyuan Zhou; Lu Liu; Wenjin Chen; et al. (Chemical Engineering Journal, 2026)

Influencing factors of soil aggregate stability under altitude-driven soil type differentiation in subtropical mountainous areas - Qiuxia Su; Yuyun Li; Caile Luo; Jinhui Yang; Wencong Liang; Feng Lu; Weisheng Luo; Qiuyue Tang; Zhiwei Qin; Xionghui Liu; Yusong Deng (CATENA, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Two new diterpenoid alkaloids from Aconitum legendrei Hand.-Mazz - Ming-Lu Zheng; Feng-Tai Qiu; Qing Tang; Lin Chen; Qin He; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Hesperidin-loaded soybean protein isolate-dextran conjugate-stabilized Pickering emulsions alleviate ulcerative colitis - Jiangfeng Xu; Shunfa Li; Jiaying Tang; Shanshan Li; Wen Qin; Qing Zhang (Food Bioscience, 2026)

Direct optical combined measurement of bubble hydrodynamics in transition flow regime of a bubble column utilizing two in-line vision probes with distinct specifications - Qin Li; Peng Zhao; Zepeng Zhao; Jie Chen; Wenxiang Tang; Haoliang Wang; Xiangyang Li; Chao Yang (Chemical Engineering Journal, 2026)

A vacancy-engineered Ce-doped NiCo-LDH electrode material for efficient, selective, and stable groundwater defluorination in FCDI systems - Xingtian Wang; Xinyue Jiang; Pengcheng Tang; Junfeng Zhu; Yuwen Wang; Huiqin Li; Dan He; Yuxuan Ma; Yuhan Qin; Boping Ren; Xiaojing Wang (Chemical Engineering Journal, 2026)

Regulating stress corrosion of biomedical Mg through microstructure and strain distribution modification - Chaokun Tang; Shaoyuan Lyu; Shuaipeng Gao; Ruixiao Zheng; Guodong Li; Zhenbo Qin; Minfang Chen (Chemical Engineering Journal, 2026)

Determinants of the variability of PGPB effects on zinc biofortification and crop yield: a meta-analysis - Hua He; Lu Peng; Jinzhi Liu; Fangchi Yang; Xiu Li; Qin Lan; Xiaoyan Tang; Yanyan Zhang; Bing Li; Changquan Wang; Yingjie Wu (Plant and Soil, 2026)

Treatment performance and mechanism of source-separated blackwater using an earthworm-based reactor for rural applications - Le Zhong; Guang-Feng Liu; Shi-Chao Liang; Jie Ding; Han-Jun Sun; Ding-Ding Tang; Yan Zhou; Xiong Qin; Ji-Wei Pang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2026)

Hydrochemical evolution driven by hyporheic exchange of the Weihe River Basin, Northwest China - Shilei Yang; Nan Li; Bin Tang; Jinxi Song; Haozheng Sun; Mengdan Guan; Ken Qin; Mengyang Yang; Zhuo Zhang (Journal of Environmental Management, 2026)

Bacillus velezensis-derived methylmalonic acid inhibits Aspergillus flavus growth and aflatoxin biosynthesis by interfering with tryptophan metabolism - Ming Li; Qin Han; Xiulan Zhao; Yuxuan Hong; Ye Zhu; Can Liu; Jinyan Chai; Ling Cheng; Xiaofeng Yue; Xiaoqian Tang; Jing Mao; Qi Zhang; et al. (Chemical Engineering Journal, 2026)

ZIF-67 derived NiCo-LDH nanoflowers in-situ Co-inherited grown on ZnO@CoCu for high performance asymmetric supercapacitors - Wenxin Chen; Tao Tang; Chaoran Lin; Hexu Wang; Dancheng Yang; Ziyi Qiao; Ming Li; Aimiao Qin; Jianfeng Wen; Guanghui Hu; Li Jiang (Chemical Engineering Journal, 2026)

Super-aligned topology-electrical regulation enhances hiPSC-derived cardiomyocyte maturation and myocardial repair - Yaning Wang; Yong Wu; Ruigong Su; Yabo Ji; Zhiru Qin; Xiaoyun Li; Miao Yu; Yi You; Miao Xiao; Wei Lei; Yang Wei; Mingliang Tang; et al. (Chemical Engineering Journal, 2026)

Efficiency and mechanisms of microbial metabolic regulator addition on carbon and nitrogen retention in biochar-assisted distilled grain waste composting - Shi-Peng Wang; Ting-Ting Wang; Xiu-Fang Li; Min Gou; Song-Tao Wang; Zhao-Yong Sun; Yue-Qin Tang (Bioresource Technology, 2026)

Construction of recombinant Lactococcus lactis expressing VP1 from duck hepatitis a virus types 1 and 3 and evaluation of its immune effect - Yafei Qin; Yaru Fan; Meijuan Zhang; Saisai Zhao; Xinhong Man; Dalin He; Youxiang Diao; Junxun Li; Jingdong Hu; Yi Tang (Veterinary Research Communications, 2026)

The structures and functions of Salmonella outer membrane - Xinliang Liu; Hongwei Zheng; Jiaqi Ma; Jiade Zhao; Yuan Ma; Jinxin Sun; Zhiwei Guo; Yu Wang; Yifei Li; Yizhen Wang; Hongjie Yang; Lei Liu; et al. (Archives of Microbiology, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

Three-dimensional WFAM for unsaturated hydraulic conductivity measurement: Theoretical derivation and numerical validation - Xiao-kang Li; Yuan-ming Lai; Xu Li; Wen-zhen Tang; Qin-guo Ma; Xiao-xiao Luo; Lun-yang Zhao (Journal of Hydrology, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

An innovative triple-channel probing strategy for ultrasensitive detection of quercetin in food matrices based on carbon dots - Ping Li; Zhen-quan Yang; Lixia Xiao; Xuechao Xu; Tianzu Guan; Wenyuan Zhou; Xiaowei Tang; Xiaojuan Gong; Qin Hu (Food Chemistry, 2026)

Environmental drivers and chlorophyll fluorescence parameter-based predictive modeling of benthic algal proliferation in the middle Route of the South-to-North water diversion project - Yifan Tang; Hongjie Qin; Si Wu; Zhicong Wang; Zeyu Jin; Genbao Li; Dunhai Li (Environmental Research, 2026)

Adding lycopene to the freezing media enhances the quality, antioxidant capacity, and fertilization ability of frozen-thawed Oure-type Tibetan sheep (Ovis aries) sperm - Yujie Tang; Hong Wu; Lidan Liu; Yanbing Liu; Haoqiang Qin; Mingxia Li; Deqing Yan; Chengtu Zhang; Jianmin Su (Cryobiology, 2026)

Ecological impacts of offshore wind power construction and operation on zooplankton communities in South China sea - Zhenzhen Peng; Mengchen Lu; Wenwen Huang; Yi Tang; Shubing Li; Huaming Qin; Lili Wang; JinShao Ye; Yan Long (Marine Pollution Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Scale-dependent effects of road hierarchy and species dispersal capacities on ecological connectivity in urban agglomerations - Xiuquan Li; Jinyi Li; Binbin Ma; Zhongan Tang; Dongshui Zhang; Chaokui Li; Qin Tian; Chen Yang; Yingwei Yan (Journal of Cleaner Production, 2026)

Morphological and physiological adaptations of Dolichospermum flos-aquae to turbulence - Yulin Wang; Wenting Zhong; Ruiwen Chen; Qin Tang; Gongzheng Li; Zhou Yang; Yuan Huang (Harmful Algae, 2026)

Gel properties of whole soybean curd reinforced by soybean protein isolate amyloid fibrils: Formation mechanism and texture enhancement - Junpeng Chen; Yantao Li; Jiaying Tang; Suqing Li; Wen Qin; Qing Zhang (Food Research International, 2026)

Impact of complex inhibitors in straw hydrolysates on xylose-fermenting Saccharomyces cerevisiae and inhibitor-tolerant strain construction - Xue-Xue Ji; Bo Li; Rong-Rong Chen; Zi-Yuan Xia; Cai-Yun Xie; Yue-Qin Tang (Fungal Biology, 2026)

Linking runoff and sediment characteristics to karst development degree in small watershed - Zhengyi Tang; Rui Li; Li Qin; Tao Song; Benjin Yu; Pingping Yang; Jun Jing; Linlv Xiao (CATENA, 2026)

Soil quality and key bacteria mediate slash mulching-induced growth and carbon storage improvements in Eucalyptus plantations - Qin Ke; Lingyue Zhu; Junyu Zhao; Kangting Huang; Liangfen Li; Yilin Weng; Jianke Wen; Xiuhai Wang; Lijun Chen; Sheng Lu; Zuoyu Qin; Lichao Wu; et al. (Applied Soil Ecology, 2026)

Can river damming amplify or dampen climate-driven changes in fluvial sediment transport? A case study of Jinsha river basin - Jianfei Wu; Qiang Liu; Liqiao Liang; Yuting Yang; Zhiqiang Tang; Jifa Qin; Shuzhen Li; Xuan Wang; Chunhui Li (Journal of Hydrology, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Emerging evidence of nighttime mercury oxidation driven by nitrate radical-activated heterogeneous halogen chemistry - Yan Wang; Zhenya Duan; Yi Tang; Shuxiao Wang; Zhijian Li; Qin Wang; Jiaming Fu; Qingru Wu (Journal of Hazardous Materials, 2026)

NADH-driven bioreductive degradation of azo dyes: Mechanisms of high NADH production, electron transfer, and microbial responses - Yiting Qin; Xuehui Xie; Dongyang Li; Ziyi Wu; Jiajie Liu; Wanting Li; Daijie Tang; Songwei Chen; Yiwen Zhang; Na Liu; Qingyun Zhang; Ye Chen (Journal of Hazardous Materials, 2026)

Cobalt-Te-Au occurrence, genesis, and metallogenic potential of the Jiama skarn orebody, Tibet, China - Shuo Wang; MingJian Cao; DongMei Tang; Noreen J. Evans; GuangMing Li; Wangdui Silang; KeZhang Qin (Journal of Asian Earth Sciences, 2026)

Signature aroma compounds and precursors in Chinese indigenous pork: Characterization via OAV-weighted GC-O-MS and lipidomic profiling - Yiyu Yin; Kehan Ma; Pingyang Li; Yingsen Liu; Liyuan Zhao; Chaohua Tang; Qingyu Zhao; Junmin Zhang; Yanan Yu; Yuchang Qin (Food Chemistry, 2026)

Identification, evolutionary and characteristic analysis of apoptosis - related caspase gene family in Tachysurus fulvidraco and their expression profiles under bacterial, parasitic, and viral infections - Peng Tang; Yueping Chen; Tong Yue; Zhangyan Liang; Jianying Yang; Qiao Wang; Yang He; Chuanjie Qin; Zhengyong Wen; Qingchao Shi; Li Zhou; Jun Wang (Fish & Shellfish Immunology, 2026)

A multiphysics coupling platform for natural gas hydrate modeling: centroidal voronoi tessellation mesh and sequential solution strategy - Zhigang You; Jiaxin Sun; Gang Lei; Xiaodong Li; Fanfan Qin; Zichun Tang; Xiwei Gao; Fulong Ning (Computers and Geotechnics, 2026)

Dissimilatory nitrate reduction to ammonium-induced false stability masks dysfunctional Candidatus Brocadia failure during ANAMMOX start-up from municipal activated sludge - Ying Qiu; Tong Yang; Jiarong Tang; Bikai Zhao; Haixiang Li; Wei-Qin Zhuang; Lijie Zhou (Bioresource Technology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

A novel recombinant serotype 4 fowl adenovirus efficiently protects both serotype 4 and 11 fowl adenovirus - Shi Liu; Ye Tang; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Quan Xie; Wei Gao; Jianqiang Ye (Veterinary Microbiology, 2025)

Corrigendum to “Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region” [Sci. Total Environ. 946 (2024) 174054] - Xiaoping Xin; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; Ruirui Yan; et al. (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Advances in active dust mitigation technologies for spacesuits - Linghao Li; Xiaolin Qin; Pengzhen Guo; Ruxian Tang; Dingkun Gao; Yun Chen; Zin Min Khant; Haibo Gao; Rongqiang Liu; Zongquan Deng; Lifang Li (Journal of Space Safety Engineering, 2025)

Enhanced impact of future temperature on Northern Hemisphere snowfall - Lina Liu; Liping Zhang; Qin Zhang; Gangsheng Wang; Zhiling Zhou; Xiao Li; Zhenyu Tang; Jun Xia (Journal of Hydrology, 2025)

Utilizing food waste hydrolysate for enhanced microalgae protein production: a step towards circular economy - Sana Irshad; Ting Tang; Asad Nawaz; Yibing Zu; Zhihui Yuan; Yanming Li; Xu Liao; Zunhua Li; Meifeng Wang; Liangping Ni; Zuodong Qin (Journal of Cleaner Production, 2025)

Bioremediation of cadmium-phoxim co-contamination by an autochthonous pollutant-resistant consortium enhances Ligusticum Chuanxiong Hort. resistance - Jianpeng Li; Minghui Wu; Han Wu; Qin Han; Yongxiang Gao; Maoxiang Tang; Can Wang; Fangfang Yan; Bin Li; Xing Li; Zhongping Qiu (Journal of Environmental Sciences, 2025)

Arabinoxylan‐sodium caseinate conjugates enhanced oxidative stability of sodium caseinate stabilized oil-in-water emulsion - Shanshan Li; Xueqing Ma; Jiaying Wei; Cheng Li; Hong Chen; Jing Yan; Mingrui Chen; Qing Zhang; Jiaying Tang; Yiqin Zhang; Wen Qin (Food Chemistry, 2025)

Dynamic DIA proteomics of mare's milk reveals distinct colostrum signatures and stage-specific lactation profiles - Luan Yue; Wendan Tang; Cao Li; Xiaoyu Yue; Xiaoyun He; Aleksandr Mikhailovich Zaitsev; Mu Zhang; Valery Vasilievich Kalaschnikov; Jingyi Li; Qin Wang (Food Chemistry, 2025)

Impacts of gluten protein characteristics on the cracking behavior of dumpling wrappers during freeze-thaw cycles - Li-qin Tang; Xiaohong Sun; Xiao-Na Guo; Ke-Xue Zhu (Food Chemistry, 2025)

Targeted screening of pancreatic lipase inhibitory peptides from quinoa protein hydrolysates by ligand fishing - Zeyue Fu; Junhao Wang; Chunxiao Wu; Jinfan Qin; Byung-Hoo Lee; Man Li; Qingjie Sun; Wenting Tang (Food Chemistry, 2025)

Grass carp HB-EGFa enhances resistance to Aeromonas hydrophila infection by fortifying gut mucosal barrier function - Pingyuan Li; Chuyi Zeng; Yujun Liu; Jiayi Hu; Ye Yang; Yiyang Tang; Zejun Zhou; Qinbo Qin (Fish & Shellfish Immunology, 2025)

NGBoost-based probabilistic surrogate modeling for rockfill dam settlements considering rockfill spatial variability - Qin Ke; Dian-Qing Li; Xiao-Song Tang (Computers and Geotechnics, 2025)

Photothermally tunable hydrogel for adaptive electromagnetic wave control and self-powered monitoring - Yi Gao; Jingyuan Tang; Qian Yang; Hongbo Hou; Renchi Qin; Tinghao Liao; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2025)

Biochar alleviates ammonium-induced suppression of methane uptake in a subtropical forest soil - Jiashu Zhou; Yanfei Dong; Caixian Tang; Zhenhui Jiang; Xinzhang Song; Mouliang Xiao; Hua Qin; Yunying Fang; Xiaokai Zhang; Tida Ge; Yu Luo; Shuokang Liu; et al. (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Genome-wide identification and characterization of R2R3-MYB gene family and functional exploration on MYB34 in Isatis indigotica - Yan Dong; Yan Zhang; Kaiwei Qin; Jiamin Kang; Lanying Cai; Xin Li; Xue Tang; Miao Lu; Tian’e Gao; Tao Li (Plant Biosystems, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Experimental investigation on the breakout force rapid prediction of underwater vehicles considering bottom-sitting parameters - Li Guo; Wensong Zhu; Yuchao Yuan; Hao Qin; Wenyong Tang (Ocean Engineering, 2025)

Carbon sequestration and PAH degradation in soils by a synthetic community of archaea and bacteria - Youai Zhang; Lin Xu; Wenjie Li; Xiangzhi Zuo; Lei Tang; Baozhan Wang; Chao Qin; Yanzheng Gao (Journal of Hazardous Materials, 2025)

Response of macroinvertebrate drift to dam-induced flow fluctuations: A field experiment in the Yarlung Zangbo river - Jiaxuan Tang; Qinghui Zeng; Fengbo Zhang; Baolong Zhao; Kang Zhao; Qin Yang; Long Yan; Wenhang Su; Pingfeng Li; Jinliang Zhang; Peng Hu (Journal of Environmental Management, 2025)

Sustainable and selective capture of Ca2+/Mg2+ from seawater desalination brines via hierarchical chitosan-based biochar aerogel adsorption - Wenjie Wang; Xin Li; Jiawang Qin; Chunyan Yang; Quanxun Liang; Shun Tang; Zhaoying Li; Jiale Wang; Shengchi Bai; Xiaoqi Wang; Wen Wen; Baicang Liu (Desalination, 2025)

Four new acylphloroglucinol glucoside derivatives from the leaves of Lysidice rhodostegia - Tian-Yuan Wu; Wei-Xuan Zheng; Xuan Zhou; Kai Zhao; Wei Wu; Li-Qin Zhan; Jin-Tao Fu; Qing Tang; Yu-Bo Zhang; Wen Li; Guo-Cai Wang (Natural Product Research, 2025)

Climate-mediated land use effects on soil organic carbon storage in karst ecosystems - Haiyang Guan; Yunxing Bai; Yunchao Zhou; Fenghua Tang; Jian Feng; Mei Fan; Zaike Gu; Li Qin; Tao Song; Jiaojiao Du (Journal of Soils and Sediments, 2025)

Whole-genome resequencing and transcriptomes analysis of hermaphroditism mechanisms in silver pomfret (Pampus argenteus): The role of feeding and lipid metabolism - Yaya Li; Jiabao Hu; Chongyang Wang; Shipan Zhao; Man Zhang; Youyi Zhang; Yuanbo Li; Qingqing Dai; Mengke Tang; Chunlai Qin; Zukang Feng; Shanliang Xu; et al. (Aquaculture, 2025)

Gynogenetic offspring from distant hybridization of red crucian carp × blunt snout bream: Insights into barbel origin - Zhengkun Liu; Xinyi Deng; Wanjing Peng; Siyang Li; Ling Xiong; Enkui Hu; Yan Tang; Zeyang Li; Qian Xiao; Yuhan Yang; Xu Huang; Chongqing Wang; et al. (Aquaculture, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Mechanistic insights into H2O2 activation by high-density iron single-atom catalysts for efficient water treatment: Surface-bound radical and singlet oxygen - Fuhang Xu; Cui Lai; Mingming Zhang; Zuying Yao; Dengsheng Ma; Bisheng Li; Meng Qin; Huchuan Yan; Xiuqin Huo; Xing Fan; Biting Wang; Shiyu Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic dewatering of construction foundation sludge via tripartite strategy: High-efficiency flocculation and floc skeleton reinforcement mechanism - Shixin Zhang; Jiahui Zhang; Dilin He; Yixin Zhang; Shiyu Yuan; Xiaomin Tang; Huaili Zheng; Sen Li; Yuxin Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2025)

Sustainable industrial wastewater purification: Fabrication of magnetic γ-Fe2O3@NiFe-layered double hydroxides and efficient Rhodamine B degradation without light irradiation - Yanling Wang; Yanqi Xu; Haiqing Qin; Cunjun Li; Luwen Tang; Luyang Gan; Hai Wang; Xinyu Wang; Linjiang Wang (Journal of Environmental Chemical Engineering, 2025)

Characterization of volatile flavour compounds and characteristic flavour precursors in poultry eggs based on multi-omics and machine learning - Hongqiang Li; Xiangmin Zhao; Xiaoming Li; Jing Liang; Shizhen Qin; Jinlu Li; Aiwen Zhang; Linna Xu; Defu Tang; Fuwei Li (Food Chemistry, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

Efficient recovery of lithium from the reverse osmosis concentrate of shale gas wastewater treatment: Adsorption performance and mechanism of Al-doped manganese-based adsorbent particles prepared via hydrophilic modification - Xin Li; Xifan Li; Quanxun Liang; Guijing Chen; Wenjie Wang; Jin Bao; Jiawang Qin; Shun Tang; Xiao Lin; Alberto Tiraferri; Baicang Liu (Desalination, 2025)

SCVFA chain length regulates denitrifiers & DNRA cells from cooperation to competition during nitrate bioreduction - Yongshi Liang; Manki Fu; Jiarong Tang; Haixiang Li; Lijie Zhou; Wei-Qin Zhuang (Chemical Engineering Journal, 2025)

S-scheme TiO2/biochar heterojunction derived from waste rice noodles: a low-cost waste-to-catalyst strategy for enhanced photocatalytic hydrogen production - Guangzhi Qin; Chuanyang Tang; Yang Yang; Guanzhi Ding; Minghui Li; Shuoping Chen (Chemical Engineering Journal, 2025)

Copper dependent in situ aggregation of engineered AuPt nanoalloy for on-demand photothermal-photodynamic-chemodynamic therapy with real-time guidance of AIE imaging to accurately treat malignant tumor - Jie Liu; Wenjuan Tang; Tao Liu; Qianqian Zhang; Li Chen; Longyu Qin; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2025)

Effect of ibuprofen on the behavior, histopathology, antioxidant system, DNA damage, and apoptosis of Asian freshwater clams (Corbicula fluminea) - Yun-xia Hou; Xiang-sheng Hong; Shi-yin Tang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jian-hui Qin; Jin-miao Zha (Aquatic Toxicology, 2025)

Assessment of the efficacy of Corbicula fluminea in controlling Ichthyophthirius multifiliis infections - Tian Qin; Yang-Yang Pan; Ke Huang; Wei-Shan Zhao; Ying-Zi Pan; Hong Zou; Wen-Xiang Li; Shan-Gong Wu; Gui-Tang Wang; Ming Li (Aquaculture, 2025)

Dynamic response reconstruction technique investigation of catenary submarine cables based on inverse finite element method - Li Guo; Shuo Peng; Yuchao Yuan; Wenyong Tang; Hao Qin (Ocean Engineering, 2025)

Fe and Mg isotopes as tracers of the mantle sources and ore-forming processes of the Xiarihamu magmatic Ni-Cu sulfide deposit - Qingyan Tang; Yan Zhang; Lu Li; Zhaowei Zhang; Zhuoming Li; Wei Liu; Chi Zhao; Tengda Yang; Tianyu Qin (Lithos, 2025)

Cultivar-dependent variation in metabolomic profiles and sensory characteristics of Zhuyeqing green tea (Camellia sinensis) - Chen Liu; Mengyi Ren; Meiyi Ning; Yihong Liao; Xiao Du; Li Qin; Wei Chen; Xiangyun Liu; Aimin Wu; Dejian Feng; Daiwen Chen; Liqiang Tan; et al. (Food Bioscience, 2025)

Membrane-enhanced methanogenesis efficiency and biomass retention in EGSB-AnMBR for food waste press filtrate treatment - Haojie Qin; Jianmin Liu; Wendong Chao; Jianyong Liu; Sheng Chang; Chang-Tang Chang; Tiago Martins; Yu-You Li; Hui Cheng (Environmental Research, 2025)

3D printing of a beehive-inspired tissue-engineered auricular cartilage scaffold for reconstruction of autologous microtia - Wilson Adrian Wijaya; Boqing Zhang; Jun Tang; Fengqin Song; Jingting Huang; Yuxiang Qin; Taoyu Liu; Zhenyu Zhang; Zhengyong Li; Ying Cen; Changchun Zhou (Chemical Engineering Journal, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

SCGs-based heterogeneous aerogels for low-cost and efficient solar-driven desalination - Li Zhou; Yaokang Qin; Hongwei Tang; Zhi Li; Hong Chen; Fei Pan; Renjie Chen; Haidong Ju; Wenjun Meng (Desalination, 2025)

Akkermansia muciniphila Akk11 Supplementation Attenuates MPTP-Induced Neurodegeneration by Inhibiting Microglial NLRP3 Inflammasome - Wei Wang; Shijie Shi; Mingyu Su; Ye Li; Xiaoyu Yao; Jiajun Jiang; Wenxi Yao; Xiaoling Qin; Zhe Wang; Chuanxi Tang (Probiotics and Antimicrobial Proteins, 2025)

Genetic identification and characterization of two novel loci for grain arsenic concentration in tetraploid wheat at various field environments - Zhaoyong Zeng; Dandan Ou; Li Yin; Yueyi Wu; Yuanfeng Huo; Yinggang Xu; Huaping Tang; Shu Yuan; Xuesong Gao; Yusheng Qin; Jian Ma; Guangdeng Chen (Plant and Soil, 2025)

Effects of biochar and organic fertilizer on microorganisms and aggregates and their carbon sequestration in sediment - Hongjiao Li; Jilai Gong; Meng Qin; Siqun Tang; Biao Song (Journal of Soils and Sediments, 2025)

Overexpression of MEOX2 inhibits breast cancer cell metastasis by targeting oxidative stress-induced RGS5 - Yujun Tang; Jie Luo; Bin Jiang; Jian Deng; Jiehua Li; Liuqing Qin (In Vitro Cellular & Developmental Biology - Animal, 2025)

How building height affects the global urban surface heat island from local climate zone perspective - Jiufeng Li; Zihan Liu; Xianzhe Tang; Yanqi Liu; Chao Qin; Yanlan Wu; Jun Huang (Sustainable Cities and Society, 2025)

Retrospective prediction of environmental emerging contaminants exposure using human hair: Insights into suitability, reliability, and availability - Qilong Liao; Lulu Huang; Juanjuan Yang; Shiyi Zhang; Fengshan Cai; Bin Tang; Li Li; Ruixin Qin; Xiao Yan; Weikeng Luo; Bixian Mai; Yunjiang Yu; et al. (Journal of Hazardous Materials, 2025)

Phosphate-solubilizing bacteria facilitate rhizospheric processes of Bidens pilosa L. in the phytoremediation of cadmium-contaminated soil: Link between phosphorus availability and cadmium accumulation - Yi Li; Shiyu Luo; Yiyun Fu; Chijian Tang; Xiaoxiao Qin; Dongyi Shi; Wei Lan; Yingxuan Tang; Fangming Yu (Journal of Hazardous Materials, 2025)

Dual-opto-CRISPRi-mediated dynamic regulation of fructose metabolism for high-efficiency D-allulose biosynthesis in E. coli - Yuwei Wang; Yingmengyu Qin; Tongjian Li; Dandan Tang; Yuting Lu; Wei Liu; Ling Jiang (Food Bioscience, 2025)

Involvement of nerve cord-expressed SVWC2 in pathogen recognition and defense in Macrobrachium nipponense - Muyi Li; Nan Qin; Bowen Yuan; Minghao Guo; Likun Yang; Ting Tang; Fengchao Li; Fengsong Liu (Fish & Shellfish Immunology, 2025)

Tanshinone IIA inhibits neuronal ferroptosis and relieves cerebral ischemia‒reperfusion injury by regulating miR-449a/ACSL4 - Huimin Yu; Yili Li; Yuehong Yang; Yanjin Qian; Xia Gao; Xichan Wang; Ping Zhan; Dekun Tang; Mei Qin; Yan Qian (Metabolic Brain Disease, 2025)

Causality-Guided Deep learning for streamflow predicting in a mountainous region - Xuan Tang; Guanghua Qin; Xuemei Wu; Yuting Zhao; Hongxia Li (Journal of Hydrology, 2025)

Potential impacts of polyethylene microplastics and heavy metals on Bidens pilosa L. growth: Shifts in root-associated endophyte microbial communities - Ziang He; Yanxue Wang; Yiyun Fu; Xiaoxiao Qin; Wei Lan; Dongyi Shi; Yingxuan Tang; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2025)

A novel flocculant based on "happy molecules" for the efficient removal of NSAIDs and NOM complexes: Role of parallel π-π stacking force - Shixin Zhang; Wenli Li; Yu Qin; Yao Chen; Zhen Liu; Sen Li; Longqing Tang; Huaili Zheng; Xiaomin Tang (Journal of Hazardous Materials, 2025)

Straw addition improves the stability and efficiency of high-solids anaerobic digestion of dewatered sludge via creating balanced function microbial community - Zhi Lin; Xiao-Xing Li; Zhao-Yong Sun; Min Gou; Yue-Qin Tang (Journal of Environmental Chemical Engineering, 2025)

Efficient degradation of chloridazon based on Ni-MHOF electrocatalytic anode - Fei Yin; Lanlan Qin; Yabin Li; Xiaolong Tang; Xia Zhao; Xiaopeng Huang; Dianjiang Cai; Xiaoning Jia (Journal of Environmental Chemical Engineering, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

Directional regulation of one-dimensional channel length in metal-organic frameworks for efficient xylene isomer separation in gas chromatography - Wen-Qi Tang; Yue-Wen Gu; Xiang Qi; Ye-Qin Zhou; Wang Li; Ming Xu; Zhi-Yuan Gu (Analytica Chimica Acta, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Integrated volatile metabolomics and transcriptomics provide insights into the formation of characteristic flavor in gynogenetic grass carp and its offspring - Jinhai Bai; Yan Tang; Xinyi Deng; Zhengkun Liu; Siyang Li; Enkui Hu; Ling Xiong; Wanjing Peng; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; et al. (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Vibration reduction characteristics of steel-rubber periodic damper based on finite-domain quasi-surface wave effect - Yu-xuan Qin; Yang Tang; Zhe Zhao; Hai-chao Li; Fu-zhen Pang; Zi-teng Mao (Ocean Engineering, 2025)

The clinical significance and biological function of tropomyosin 3 in ulcerative colitis - Xue-qin Zhang; Jian-mei Li; Feng-qian Wang; Yan-hui Ren; Shi-xian Wu; Yao Wu; Yuan Tang (Tissue and Cell, 2025)

Dynamic impact of polyethylene terephthalate nanoplastics on antibiotic resistance and microplastics degradation genes in the rhizosphere of Oryza sativa L. - Yi Li; Weiwei Qin; Xiaomin Xin; Chijian Tang; Yueying Huang; Xinying He; Lixing Chen; Guo Yu; Fangming Yu (Journal of Hazardous Materials, 2025)

Structural controls on the magma emplacement and distribution of sulfide orebodies in the Kalatongke Cu-Ni sulfide district, NW China - Xue-Hai Wang; Ke-Zhang Qin; Xing-Wang Xu; Dong-Mei Tang; Ya-Jing Mao; Lei Zhang; Min-Qiang Zhang; Fang-Lin Yuan; Yi Li (Journal of Asian Earth Sciences, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Mitigation effect and mechanism of different pretreatment methods on reverse osmosis membrane fouling in coal chemical wastewater treatment - Peng Tang; Jialin Shi; Can He; Xifan Li; Guijing Chen; Yi Deng; Jiawang Qin; Baicang Liu (Desalination, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Decrease in urban-rural differences of nighttime humid heatwaves in the Yangtze River Delta, China - Wenqing Zhou; Liping Zhang; Qin Zhang; Yi Li; Gangsheng Wang; Zhenyu Tang; Xiao Li; Zhengfeng Bao; Hui Cao; Benjun Jia (Atmospheric Research, 2025)

Landscapes of gut microbiome and blood metabolomic signatures in relapsing remitting multiple sclerosis - Jinzhou Feng; Shi Tang; Xiaolin Yang; Mengjie Zhang; Zhizhong Li; Shaoru Zhang; Yongliang Han; Yongmei Li; Philippe P. Monnier; Gang Yu; Peng Zheng; Cunjin Zhang; et al. (Science China Life Sciences, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Coral-Symbiodiniaceae symbiotic associations under antibiotic stress: Accumulation patterns and potential physiological effects in a natural reef - Zhicong Yan; Xiaocong Cao; Hao Su; Changqing Li; Jiamin Lin; Kai Tang; Jiahua Zhang; Hangbo Fan; Qin Chen; Jia Tang; Zhi Zhou (Journal of Hazardous Materials, 2025)

Effects of salt ions and pH on deamidated soybean protein hydrogels formation: Molecular structure, thermal aggregation and network - Tang-Hao Li; Yao-Qin Yang; Gao-Shang Wang; Ding-Yang Lv; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The H2S-releasing multifunctional composite ionic liquid facilitates topical melittin delivery for psoriasis treatment through RONS scavenging and inflammation inhibition - Meng Zeng; Ping Deng; Qin Li; Qi Tang; Jixiang Li; Liangke Zhang (Chemical Engineering Journal, 2025)

Regulating the macroscopic and microscopic self-assembly behavior of hydroxybutyl chitosan based on alkyl distribution - Shichao Bi; Guohui Sun; Tianrui Wang; Di Qin; Qiang Yu; Xiao Ma; Houxi Li; Xiguang Chen; Bo Tang (Carbohydrate Polymers, 2025)

Multi-omics analysis of the accumulation mechanism of flavonoids in rice caryopsis under blue light - Ping Zhang; Yongsheng Tang; Juxiang Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Yutao Bai; Peng Qin (Plant Cell Reports, 2025)

Sex-biased juvenile hormone and gene expression underlie sex difference of stress resistance in the American cockroach - Fangfang Liu; Shudian Zhang; Ping Chen; Wei Tang; Xiaoyi Chen; Yingting Wu; Sishi Xia; Diqi Peng; Zhengyi Shao; Qin Li; Yuqing Liu; Xiaoshuai Zhang; et al. (Journal of Pest Science, 2025)

Effect of Interaction of ATG7 and Plasma Metal Concentrations on Cognitive Impairment in Rural China - Xu Tang; Jiejing Cao; Jiansheng Cai; Xiaoting Mo; Yanfei Wei; Kailian He; Zeyan Ye; Yu Jian Liang; Linhai Zhao; Lidong Qin; You Li; Jian Qin; et al. (Journal of Molecular Neuroscience, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Investigation of Cyclospora spp. in farmed fur animals based on PCR-RFLP - Nian-Yu Xue; Hai-Tao Wang; Qing-Yu Hou; Ya Qin; Xue-Min Li; Jing Jiang; Li-Hua Yang; Xing Yang; Yan Tang (Veterinary Parasitology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Electronic engineering induced ultrafine non-noble nanoparticles for high-performance hydrogen evolution from ammonia borane hydrolysis - Siyuan Tang; Linlin Xu; Xiang Ding; Quanjiang Lv; Haotian Qin; Aosong Li; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

Solid-state ion-conductive elastomers with high mechanical robustness and ion-conductivity for highly durable triboelectric nanogenerators - Fangyan Ou; Xinze Li; Liang Tuo; Zhichao Zhang; Wei Tang; Ting Xie; Chuang Ning; Wenyu Pan; Qizhi Chen; Qihua Liang; Zhiyong Qin; Wei Gao; et al. (Chemical Engineering Journal, 2025)

Regulation of silanol nests in zeolite to form stable Td-Co(II) species for efficient propane dehydrogenation - Huihui Deng; Baozhen Li; Wenchun Zheng; Qin Sun; Mengjia Zhu; Jun Zuo; Yu Tang; Lizhi Wu; Li Tan (Chemical Engineering Journal, 2025)

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

Globular adiponectin, acting via AdipoR1, regulates food intake of Siberian sturgeon (Acipenser baerii) in a mTOR dependent manner - Ni Tang; Yingzi Li; Yuru Wu; Hongwei Wu; Qin Kang; Qin Yao; Shuhuang Chen; Youlian Liu; Kezhen Jiang; Yixiao Xiong; Jiamei Li; Xin Zhang; et al. (Aquaculture, 2025)

Membrane fouling behavior and cleaning control of a dual-charged nanofiltration membrane in treating acid mine drainage after neutralization - Yanan Jiao; Chunhui Zhang; Yuanhui Tang; Zhaowei Qin; Xuezhi Li; Peidong Su (Process Safety and Environmental Protection, 2025)

The necessity of enhancing the human health risk assessment of 1,3,6,8-tetrabromocarbazole: Based on in vitro experiments, theoretical calculations, and model predictions - Junchao Ma; Mengxi Ren; Jiangyan He; Pengcheng Shi; Dawei Xing; Xiaochao Tang; Qiang Yang; Yunhong Song; Qiang Li; Tingting Zhao; Chao Qin; Xiaoju Chen (Environmental Pollution, 2025)

Coupled vibratory roller and layered unsaturated subgrade model for intelligent compaction - Chuxuan Tang; Zheng Lu; Lang Qin; Tingzhou Yan; Jian Li; Yang Zhao; Yu Qiu (Computers and Geotechnics, 2025)

Achieving 19.3%-efficiency binary organic solar cells via synergistically dual-phases morphology control - Yushou Zhao; Wenming Li; Xiaofeng Qin; Aiqin Li; Weile Guo; Menglan Lv; Zhicai He; Yong Hua; Dianyong Tang; Bin Zhang (Chemical Engineering Journal, 2025)

Rapid gelation of mechanical robust, conductive, and self-healing lignocellulosic nanofibrils hydrogel toward flexible sensor over a broad temperature spectrum - Zhi-Chao Xu; Yu-Qin Yang; Xiao-Wen Pang; Baiyu Jiang; Peng-Fei Mao; Li-Xiu Gong; Binghao Wang; Li Peng; Long-Cheng Tang; Shi-Neng Li (Chemical Engineering Journal, 2025)

Knockdown of DJ-1 Exacerbates Neuron Apoptosis Induced by TgCtwh3 through the NF-κB Pathway - Di Yang; Minmin Wu; Nian Zou; Yiru Tang; Qing Tao; Lei Liu; Mengmeng Jin; Li Yu; Jian Du; Qingli Luo; Jilong Shen; Deyong Chu; et al. (Molecular Neurobiology, 2025)
Mutations or loss of function of DJ-1 and Toxoplasma gondii ( T. gondii ) infection has been linked to neurodegenerative diseases, which are often caused by oxidative stress. However, the relationship between DJ-1 and T. gondii infection is not yet fully understood. Therefore, this study aimed to investigate the expression of DJ-1 in the hippocampus tissue of mice or in HT22 infected with T. gondii Chinese 1 genotype Wh3 strain (TgCtwh3) and the effect of DJ-1 knockdown on neuronal apoptosis induced by TgCtwh3 tachyzoite, as well as the underlying mechanism at the cellular and molecular level. Firstly, we detected DJ-1 protein expression and cell apoptosis in the hippocampal tissue of mice infected by TgCtwh3. Then, we examined DJ-1 expression and apoptosis in HT22 challenged with TgCtwh3. Finally, we evaluated the apoptosis in HT22 with DJ-1 knockdown which was infected with TgCtwh3 and assayed the expression of NF-κBp65 and p -NF-κBp65. Our results showed that DJ-1 expression was reduced and neurons underwent apoptosis in the hippocampus of mice infected with TgCtwh3 tachyzoites. Additionally, the knockdown of DJ-1 followed by infection with TgCtwh3 tachyzoites led to increased apoptosis in HT22 cells through the NF-κB signaling pathway. Therefore, this study suggests that DJ-1 is an important target for preventing apoptosis caused by T. gondii TgCtwh3.

The chloroplast genome of Camellia sinensis var. assamica cv. Duntsa (Theaceae) and comparative genome analysis: mutational hotspots and phylogenetic relationships - Jin Li; Xiao-Yan Qiu; Yu Qin; Han Tang; Jun Tang; Tian-Tian Liu; Li-Zheng Xiao; Hua Luo (Genetic Resources and Crop Evolution, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Dimethyl trisulfide reduces postharvest anthracnose and enhances mango quality, and a potential molecular mechanism against Colletotrichum gloeosporioides - Lihua Tang; Ruyun Qin; Suiping Huang; Xiaolin Chen; Tangxun Guo; Tom Hsiang; Qili Li (Pesticide Biochemistry and Physiology, 2024)

Enhancing the inhibitory activities of polyphenols in passion fruit peel on α-Amylase and α-Glucosidase via β-Glucosidase-producing Lactobacillus fermentation - Fuhao Tang; Baoyao Wei; Chao Qin; Li Huang; Ning Xia; Jianwen Teng (Food Bioscience, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Uncovering the spatial characteristics of global net anthropogenic nitrogen input at high resolution and across 1.42 million lake basins - Jincheng Li; Yanxin Sun; Yue Qin; Ting Tang; Taher Kahil; Peter Burek; Gang Zhao; Kaikui Cai; Qingsong Jiang; Yong Liu (Science of The Total Environment, 2024)

Impacts of urban expansion on air temperature and humidity during 2022 mega-heatwave over the Yangtze River Delta, China - Wenqing Zhou; Liping Zhang; Gangsheng Wang; Qin Zhang; Hui Cao; Hairong Zhang; Benjun Jia; Zhenyu Tang; Xiao Li; Lina Liu (Science of The Total Environment, 2024)

Cellulosic ethanol stillage for methane production by integrating single-chamber anaerobic digestion and microbial electrolysis cell system - Tian-Jie Ao; Jie Wu; Kai Li; Richard Chandra; Xin-Qing Zhao; Yue-Qin Tang; Chen-Guang Liu; Feng-Wu Bai (Science of The Total Environment, 2024)

Bioelectrochemical technologies for soil and sediment remediation: Recent advances and future perspectives - Linlan Zheng; Xixi Cai; Jiahuan Tang; Hongjie Qin; Jibing Li (Journal of Environmental Management, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Regulated charge transfer by cascade dual Z-scheme heterojunction of HCdS@ZnIn2S4-Cobalt porphyrin for efficient photocatalytic solar fuel production - Tengfei Bao; Chenxi Tang; Shuming Li; Ping She; Heng Rao; Jun-sheng Qin (Chemical Engineering Journal, 2024)

Moist-electric generators using biomass Juncus effusus fibers with 3D microchannels for wearable applications - Lingling Su; Chunhua Zhang; Wenyang Tang; Zhuan Fu; Junyao Gong; Jieyao Qin; Li Li; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2024)

Regulation of macroporous cellulose microspheres via phase separation force induced by carbon nanotubes doping for enhanced protein adsorption - Qin Wang; Yanjie Li; Zhangyong Tang; Kaifeng Du (Carbohydrate Polymers, 2024)

Unveiling potential sex-determining genes and sex-specific markers in autotetraploid Carassius auratus - Kun Zhang; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; Xiaoping Dong; Qingwen Xiao; Jinhai Bai; Yue Zhou; Zhengkun Liu; Xinyi Deng; Yan Tang; et al. (Science China Life Sciences, 2024)

Physiological and metabolic responses of Sophora tonkinensis to cadmium stress - Fan Wei; Hao Chen; Guili Wei; Danfeng Tang; Changqian Quan; Meihua Xu; Linxuan Li; Shuangshuang Qin; Ying Liang (Physiology and Molecular Biology of Plants, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Bioavailability and ecological risk assessment of metal pollutants in ambient PM2.5 in Beijing - Yunzhe Li; Yanyi Qin; Lisha Zhang; Linxi Qi; Shuifeng Wang; Jinghua Guo; Aohan Tang; Keith Goulding; Xuejun Liu (Science of The Total Environment, 2024)

Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region - Xiaoping Xin; Xueqi Lan; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; et al. (Science of The Total Environment, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

A novel nanofiltration membrane with a dual-charged layer to simultaneously remove anions and cations from acid mine drainage - Yanan Jiao; Chunhui Zhang; Yuanhui Tang; Zhaowei Qin; Xuezhi Li; Tengzhuo Zhang; Zhao Zhang; Zhiwei Lin; Peidong Su (Process Safety and Environmental Protection, 2024)

Numerical simulation and experimental study of hydrodynamic characteristics of inverted-droplet underwater gas storage devices - Chaoqun Liu; Yingchun Xie; Haoxun Yuan; Jin Qin; Xiangkun Li; Xiancai Si; Yuanlong Tang (Ocean Engineering, 2024)

Formation of a transparent soy protein hydrogel: Controlled thermal aggregation of protein using glutaminase - Tang-Hao Li; Yao-Qin Yang; Ding-Yang Lv; Gao-Shang Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

A carboxymethyl cellulose/chitosan-based hydrogel harvests robust adhesive, on-demand detachment and self-healing performances for deep burn healing - Mengya Li; Haofan Qu; Qin Li; Shengchang Lu; Yang Wu; Zuwu Tang; Xiaolong Liu; Zhanhui Yuan; Liulian Huang; Lihui Chen; Hui Wu (Chemical Engineering Journal, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Correction to: Identification of predictors for neurological outcome after cardiac arrest in peripheral blood mononuclear cells through integrated bioinformatics analysis and machine learning - Zhonghao Li; Ying Qin; Xiaoyu Liu; Jie Chen; Aling Tang; Shengtao Yan; Guoqiang Zhang (Functional & Integrative Genomics, 2024)

Diet along the eastern Silk Roads: an isotopic case study of ancient humans and livestock from the Han-Jin Dynasties in the Lop Nur region, northwest China - Xueye Wang; Kangkang Li; Dong Wei; Guiying Zhang; Xingjun Hu; Jing Feng; Yingxin Jiao; Bing Xu; Xiaoguang Qin; Vicky M. Oelze; Zihua Tang (Archaeological and Anthropological Sciences, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Immunosuppressive alkaloids from Narcissus tazetta subsp. Chinensis and the mechanism of (+)-narciclasine in vitro and in vivo - Wen-Ling Wang; Xiu-Yin Wu; Xing-Yan Luo; Yu-Qin Tang; Jia Cui; Xin-Yue Huang; Yu-Chen Jiang; Yang Liu; Li-Mei Li (Phytochemistry, 2024)

Lanthanum ferrite modified filling materials and its enhancement for phosphorus and COD removal: Performance and mechanism - Qing Li; Bei Yang; Xinyu Chen; Yuting Han; Qin Chen; Shiying He; Yanfang Feng; Yancan Wu; Xiaohui Liang; Lihong Xue; Jie Tang (Journal of Water Process Engineering, 2024)

Difference between traditional brewing technology and mechanized production technology of jiangxiangxing baijiu: Micro ecology of zaopei, physicochemical factors and volatile composition - Lianqing Wang; Ping Tang; Qing Zhao; Qimuge Shan; Liqin Qin; Dongguang Xiao; Changwen Li; Jun Lu; Xuewu Guo (Food Research International, 2024)

Fermentation of Soy-based dairy substitutes by lactic acid bacteria: Focus on the process of soy protein hydrolysis - Zengbo Wang; Xiaodong Wang; Congrui Zhao; Hongwei Tang; Jiage Ma; Qi Qin; Kuangyu Zhao; Wei Yu; Bailiang Li (Food and Bioproducts Processing, 2024)

Efficient uranium sequestration ability and mechanism of live and inactivated strain of Streptomyces sp. HX-1 isolated from uranium wastewater - Gen Xie; Guangwen Feng; Qin Li; Keyong Zhang; Chao Tang; Henglei Chen; Changlong Cai; Peihong Mao (Environmental Pollution, 2024)

A 2D self-cascade catalytic system based on CoCuFe-LDH nanosheets for accelerated healing of infected wounds - Jinyao Zheng; Zongjia Li; Juan Qin; Yuanhao Zhang; Xinyue Guo; Xiue Jiang; Miaomiao Zhang; Jilin Tang (Chemical Engineering Journal, 2024)

Unveiling the Pharmacological Role of Human Deubiquitinating Enzymes in Temozolomide Response of Glioblastoma Cells - Chunguang Yang; Yifei Li; Qifan Wu; Jiayi Tang; Min Chen; Baoyu Zhang; Bowen Li; Yunfei Qin; Guobin Huang; Yize Zhang; Feng Zhi; Kunpeng Liu (Cell Biochemistry and Biophysics, 2024)

GDNF's Role in Mitigating Intestinal Reactive Gliosis and Inflammation to Improve Constipation and Depressive Behavior in Rats with Parkinson’s disease - Qin Xiaoling; Guo Yurong; Xue Ke; Qiu Yuxiang; An Panpan; Du Yinzhen; Li Xue; Liu Tingting; Tang Chuanxi (Journal of Molecular Neuroscience, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Cu single atoms mediated multiple active site reconfiguration to trigger Dual-pathway nonradical peroxymonosulfate activation process - Deyu Qin; Chen Zhang; Fanzhi Qin; Yin Zhou; Danlian Huang; Hou Wang; Hanzhuo Luo; Qi Wang; Lin Tang; Wenwei Li (Chemical Engineering Journal, 2024)

Microreactors with multivariate external force field used for the chemical process intensification - Tingting Ma; Shuangfei Zhao; Weiwei Tang; Weiwei Zhong; Yuhang Liu; Yirong Feng; Zheng Fang; Hong Qin; Hong Xu; Yuguang Li; Yue Zhao; Fanrong Meng; et al. (Chemical Engineering Journal, 2024)

Ucf-101 alleviates Ischaemia/Reperfusion induced retinal inflammation and injury via suppressing oxidative damage - Yuan-Jun Qin; Guangyi Huang; Jing Liao; Li Jiang; Fen Tang; Ningning Tang; Yiyi Hong; Chaolan Shen; Qianqian Lan; Fan Xu; Lifei Chen (Journal of Molecular Histology, 2024)

Soil aggregate size mediates the variations in the abundance and function of ammonia oxidizers in heavy metal-contaminated soil under different nitrogen fertilization regimes - Xian Huang; Shuting Tang; Meng Zeng; Zhongkai Qin; Jialiang Liang; Yuyuan Chen; Yamei Wu; Shuairen Chen; Fangming Yu; Yi Li (Applied Soil Ecology, 2024)

Integrating metabolomics and network pharmacology to evaluate the effectiveness of traditional medicinal parts of Chinese herbal medicine Cassia agnes Brenan - Qin Liu; Kuanying Tan; Yi Liu; Xiaohan Tang; Weiqiong Li; Jifei He; Yafang Li; Tao Li; Minggao Zi; Hongyan Yang; Yuyi Chai (South African Journal of Botany, 2024)

Effect of polyethylene microplastics on antibiotic resistance genes: A comparison based on different soil types and plant types - Yi Li; Xinwei Shi; Meng Zeng; Peiqing Qin; Mingyue Fu; Shiyu Luo; Chijian Tang; Cuiju Mo; Fangming Yu (Journal of Hazardous Materials, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Integrative Metabolomics and Whole Transcriptome Sequencing Reveal Role for TREM2 in Metabolism Homeostasis in Alzheimer’s Disease - Meng Wang; Tao Wei; Chaoji Yu; Ruiyang Li; Yunsi Yin; Hanchen Yang; Run Di; Xinyi Xia; Qi Qin; Yi Tang (Molecular Neurobiology, 2024)

Plastome structure, phylogeny and evolution of plastid genes in Reevesia (Helicteroideae, Malvaceae) - Li-Yang Geng; Tian-Yi Jiang; Xin Chen; Qiang Li; Jian-Hui Ma; Wen-Xiang Hou; Chen-Qian Tang; Qin Wang; Yun-Fei Deng (Journal of Plant Research, 2024)

Dominant role of the non‐forest woody vegetation in the post 2015/16 El Niño tropical carbon recovery - Lei Fan; Tianxiang Cui; Jean‐Pierre Wigneron; Philippe Ciais; Stephen Sitch; Martin Brandt; Xin Li; Shuli Niu; Xiangming Xiao; Jérome Chave; Chaoyang Wu; Wei Li; et al. (Global Change Biology, 2024)
The extreme dry and hot 2015/16 El Niño episode caused large losses in tropical live aboveground carbon (AGC) stocks. Followed by climatic conditions conducive to high vegetation productivity since 2016, tropical AGC are expected to recover from large losses during the El Niño episode; however, the recovery rate and its spatial distribution remain unknown. Here, we used low‐frequency microwave satellite data to track AGC changes, and showed that tropical AGC stocks returned to pre‐El Niño levels by the end of 2020, resulting in an AGC sink of Pg C year −1 during 2014–2020. This sink was dominated by strong AGC increases ( Pg C year −1 ) in non‐forest woody vegetation during 2016–2020, compensating the forest AGC losses attributed to the El Niño event, forest loss, and degradation. Our findings highlight that non‐forest woody vegetation is an increasingly important contributor to interannual to decadal variability in the global carbon cycle.

Three types of enzymes complete the furanocoumarins core skeleton biosynthesis in Angelica sinensis - Kaixuan Wang; Huihui Zeng; Yiqun Dai; Zixuan Wang; Huanying Tang; Junde Li; Xingchen Lu; Neng Jiang; Guoyong Xie; Yan Zhu; Yucheng Zhao; Minjian Qin (Phytochemistry, 2024)

Development and application of intelligent packaging films based on carboxymethyl starch/PVA with Cu-LTE nanocrystal as functional compatibilizer - Nannan Li; Hai Qin; Qun Tang; Daijiang Peng; Xiaoyan Luo; Heping Li; Zhiming Zou (Food Packaging and Shelf Life, 2024)

Retraction Note: Comparison of preoperative ultrasound and MRI in the diagnosis of microvascular invasion in hepatocellular carcinoma - Yunmin Long; Zheng Lv; Shaoyi Wang; Bing Tang; Qin Li; Wei Zhang (Functional & Integrative Genomics, 2024)

Neglected function of gastrin to reduce feeding in Siberian sturgeon (Acipenser baerii) via cholecystokinin receptor B - Shupeng Zhang; Yongpei Lu; Yanling Liu; Mei Wang; Shaoqi Xu; Ya Li; Hongwei Wu; Qaolin Pei; Lei Yang; Lu Lu; Yixiao Xiong; Youlian Liu; et al. (Fish Physiology and Biochemistry, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

AlphaLISA-Based Immunoassay for Detection of Troponin T in Serum of Patients with Acute Myocardial Infarction - Wei Lv; Qian Li; Yan Tang; Yuan Qin; Xiumei Zhou; Xueqin Zhao; Zhencang Zheng; Biao Huang (Journal of Fluorescence, 2024)

A hybrid method for assessing the city emission status toward carbon peak - Jianhui Ruan; Ziyu Qin; Shuangyue Qian; Mingyu Li; Min Jia; Li Zhang; Zhe Zhang; Shuying Zhu; Hanying Jiang; Bofeng Cai; Shouyang Wang; Ling Tang (Urban Climate, 2024)

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Early Cretaceous magmatism archives crustal architecture of northern Lhasa Terrane, central Tibetan Plateau - Wan-Li Tang; Feng Huang; Zheng-Wei Qin; Yun-Chuan Zeng; Ji-Feng Xu (Lithos, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Bisphenols can promote antibiotic resistance by inducing metabolic adaptations and natural transformation - Jingyu Qin; Xin Qi; Yuejiao Li; Zhuyun Tang; Xiaona Zhang; Shaoguo Ru; Jiu-Qiang Xiong (Journal of Hazardous Materials, 2024)

Microplastics enhance the invasion of exotic submerged macrophytes by mediating plant functional traits, sediment properties, and microbial communities - Xiaowei Li; Hongjie Qin; Na Tang; Xiaolu Li; Wei Xing (Journal of Hazardous Materials, 2024)

A systematic comparison of salt removal efficiency in washing treatment by using fly ashes from 13 MSWI plants in China - Gangzhen Jiao; Yunmei Wei; Qin Liao; Sijie Liu; Shengjun Tang; Zihan Li (Journal of Environmental Management, 2024)

Research progress of microfluidics-based food safety detection - Wenjun Jiang; Qu Tang; Yidan Zhu; Xijuan Gu; Li Wu; Yuling Qin (Food Chemistry, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Immediate and delayed effects of environmental temperature on schizophrenia admissions in Liuzhou, China, 2013–2020: a time series analysis - Qian Zhou; Xiaolan Huang; Li Su; Xianyan Tang; Yanli Qin; Yuting Huo; Chun Zhou; Jun Lan; Yue Zhao; Zaifei Huang; Guoguang Huang; Yuhua Wei (International Journal of Biometeorology, 2024)

Wildfires in Southeast Asia pollute the atmosphere in the northern South China Sea - Yujie Qin; Haichao Wang; Yiming Wang; Xiao Lu; Hairong Tang; Jianqing Zhang; Lei Li; Shaojia Fan (Science Bulletin, 2024)

Biotransformation of the azo dye reactive orange 16 by Aspergillus flavus A5P1: Performance, genetic background, pathway, and mechanism - Wen Qin; Shiqi Guo; Qingyun Li; Aixing Tang; Haibo Liu; Youyan Liu (Journal of Hazardous Materials, 2024)

Ligand structure optimization leads to efficient acid-resist Am(III)/Eu(III) separation in n-octanol - Yaoyang Liu; Mingjie Bao; Ludi Wang; Yu Kang; Yangcheng Dou; Jiaojiao Qin; Fan Guo; Huaixin Hao; Zhipeng Wang; Xiaoyan Tang; Jing Chen; Li Wang; et al. (Chemical Engineering Journal, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Important role of DNA methylation hints at significant potential in tuberculosis - Yuexuan Qin; Tianyue Li; Peiyan An; Zhi Ren; Jun Xi; Bikui Tang (Archives of Microbiology, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Remote and local controls on dissolved oxygen in the Western Tropical Pacific thermocline during the last 700 kyr - Zheng Tang; Tiegang Li; Zhifang Xiong; Bingbin Qin; Peiying Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Integrated morphological, physiological and transcriptomic analyses reveal response mechanisms of rice under different cadmium exposure routes - Qin Dong; Yingjie Wu; Haidong Wang; Bing Li; Rong Huang; Huanxiu Li; Qi Tao; Qiquan Li; Xiaoyan Tang; Qiang Xu; Youlin Luo; Changquan Wang (Journal of Hazardous Materials, 2024)

A review on the antibiotic florfenicol: Occurrence, environmental fate, effects, and health risks - Xingying Guo; Haibo Chen; Yongqi Tong; Xintong Wu; Can Tang; Xian Qin; Jiahua Guo; Ping Li; Zhen Wang; Wenhua Liu; Jiezhang Mo (Environmental Research, 2024)

Lithium recovery from the spent lithium-ion batteries by commercial acid-resistant nanofiltration membranes: A comparative study - Sheng-Li Gao; Zi-Xuan Qin; Bo-Fei Wang; Jie Huang; Zhen-Liang Xu; Yong-Jian Tang (Desalination, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Successive landsliding on the G213 National Highway, a section of the Sichuan-Qinghai traffic corridor (May 10, 2023, Songpan County, Sichuan, China) - Yizhi Li; Shunyu Huang; Peng Tang; Yichao Wang; Gianvito Scaringi; Enlong Liu; Minghui Meng; Liang Qin (Landslides, 2024)

Quantitative Proteomics Reveals Manganese Alleviates Heat Stress of Broiler Myocardial Cells via Regulating Nucleic Acid Metabolism - Shizhen Qin; Rui Wang; Jinlu Li; Defu Tang; Zhaoguo Shi (Biological Trace Element Research, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Black shale LA-ICP-MS Rb-Sr and monazite SIMS U-Pb geochronology from the Cryogenian successions in the northern Yangtze Block - Zhongwu Lan; Kyle Larson; Rong Cao; Qin Ye; Jun Hu; Guoqiang Tang; Jiao Li; Jinnan Tong (Precambrian Research, 2024)

Enhanced atmospheric water harvesting (AWH) by Co-based MOF with abundant hydrophilic groups and open metal sites - Sihan Li; Peng Wu; Long Chen; Yiwen Tang; Yanhe Zhang; Ling Qin; Xiaofei Qin; Haibo Li (Journal of Water Process Engineering, 2024)

A Yokenella regensburgei strain effectively removes Cu(II), Pb(II), and Cd(II) through a combination of absorption and mineralization modes - Yijia Xu; Yanhua Qi; Jin Xie; Qijian Qin; Gang Huang; Peiduo Tang; Cheng Jin; Bin Wang; Youzhi Li; Wenxia Fang (Journal of Water Process Engineering, 2024)

Bright photoactivatable probes based on triphenylethylene for Cu2+ detection in tap water and tea samples - Zuo-Qin Liang; Dong-Dong Song; Zhuo-Cheng Li; Su-Hang Xu; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang; Xu-Tang Tao (Food Chemistry, 2024)

Selected pesticidal POPs and metabolites in the soil of five Vietnamese cities: Sources, fate, and health risk implications - Yang Ding; Shibin Qin; Huanfang Huang; Xiaoyan Tang; Xiushuang Li; Yuan Zhang; Wenwen Chen; Lan-Phuong Nguyen; Shihua Qi (Environmental Pollution, 2024)

Environmental selenium and human longevity: An ecogeochemical perspective - Bo Li; Xu Liu; Tao Yu; Kun Lin; Xudong Ma; Cheng Li; Zhongfang Yang; Qifeng Tang; Guodong Zheng; Jianxun Qin; Ying Wang (Chemosphere, 2024)

Brain-derived neurotrophic factor (BDNF) activates PI3K-AKT-mTOR signaling via hypothalamic TrkB receptors to reduce feeding in Siberian sturgeon (Acipenser baerii) - Shupeng Zhang; Yongpei Lu; Yingzi Li; Yanling Liu; Qin Yao; Qin Kang; Shuhuang Chen; Youlian Liu; Yixiao Xiong; Defang Chen; Xin Zhang; Ni Tang; et al. (Aquaculture, 2024)

Examining the supplementation of exogenous lipid and antioxidant to improve the survivability of post-thaw oocytes in Mediterranean mussels, Mytilus galloprovincialis - Xiaochen Zhu; Penny Miller-Ezzy; Mark Gluis; Jianguang Qin; Youhong Tang; Yibing Liu; Yingying Zhao; Xiaoxu Li (Aquaculture, 2024)

Selenomethionine protects the liver from dietary deoxynivalenol exposure via Nrf2/PPARγ-GPX4-ferroptosis pathway in mice - Shijie Fan; Luxi Lin; Pingyang Li; Huihui Tian; Jialu Shen; Longzhu Zhou; Qingyu Zhao; Junmin Zhang; Yuchang Qin; Chaohua Tang (Toxicology, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Interfacial bidirectional binding for improving photovoltaic performance of perovskite solar cells - Mengmeng Chen; Ke Tian; Hairui Liu; Yang Liu; Ying Tang; Shan Cong; Zhenhuang Su; Feng Yang; Zhuxia Zhang; Songhua Chen; Chaochao Qin; Jien Yang; et al. (Chemical Engineering Journal, 2024)

Inverse kinetic isotope effect of proton and deuteron permeation through pyridinic N-doped graphene - Jingwen Ba; Jinfan Chen; Renjin Xiong; Jingsong Xu; Haibo Li; Xiayan Yan; Cheng Qin; Rui Li; Qifa Pan; Xinxin Tan; Tao Tang; Xin Xiang; et al. (Chemical Engineering Journal, 2024)

Lipopolysaccharide alters VEGF-A secretion of mesenchymal stem cells via the integrin β3-PI3K-AKT pathway - Shuya Mei; Shaojie Qin; Ri Tang; Qiaoyi Xu; Yue Hu; Jinhua Feng; Zhengyu He; Yuan Gao; Hui Li; Shunpeng Xing (Molecular & Cellular Toxicology, 2024)

Isolation, identification, and induced differentiation of satellite cells from skeletal muscle of adult tree shrews - Shenghui Ke; Yiwei Feng; Liying Luo; Wanzhao Qin; Huayu Liu; Jingchong Nie; Beijiang Liang; Hongjie Ma; Mao Xie; Jingyu Li; Zhijie Niu; Guojian Li; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)

Correction to: Protective Efect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2024)

Association of glyphosate exposure with multiple adverse outcomes and potential mediators - Wenxiang Li; Daizai Lei; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yunru Lin; Fan Xu; Yuan-jun Qin (Chemosphere, 2023)

Association between multiple metals exposure and sleep disorders in a Chinese population: A mixture-based approach - Lu Yufu; Liu Qiumei; Zhang Tiantian; Cai Jiansheng; Tang Xu; Wei Yanfei; Mo Xiaoting; Huang Shenxiang; Lin Yinxia; Li You; Luo Tingyu; Qin Jian; et al. (Chemosphere, 2023)

A simplified analytical method for the tunnels’ mechanical behaviour under the action of active fault zones - Li Yu; Xiao Zhang; Mingnian Wang; Henghong Yang; Xun Luo; Youlin Qin; Langzhou Tang (Computers and Geotechnics, 2023)

High-performance supercapacitor and ultra-sensitive humidity sensor based on bifunctional NiCo2O4/g-C3N4 nanocomposites powered by triboelectric nanogenerator - Likun Gong; Zhaozheng Wang; Junqing Zhao; Jiajun Tang; Zheng Li; Weiqi Meng; Zhipeng Qiu; Yuhan Qin; Xingwei Wang; Chi Zhang; Dongzhi Zhang (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Environmental pollutants induce NLRP3 inflammasome activation and pyroptosis: Roles and mechanisms in various diseases - Yu Mou; Wenhao Liao; Yun Liang; Yuchen Li; Mei Zhao; Yaoyao Guo; Qin Sun; Jianyuan Tang; Zhilei Wang (Science of The Total Environment, 2023)

Metagenomics reveals taxon-specific responses of soil nitrogen cycling under different fertilization regimes in heavy metal contaminated soil - Xinwei Shi; Weilan Tan; Shuting Tang; Qiujie Ling; Chijian Tang; Peiqing Qin; Shiyu Luo; Yinjun Zhao; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

A comprehensive review of deep coalbed methane and recent developments in China - Song Li; Yong Qin; Dazhen Tang; Jian Shen; Junjian Wang; Shida Chen (International Journal of Coal Geology, 2023)

Determination of the effects of pre-harvest bagging treatment on kiwifruit appearance and quality via transcriptome and metabolome analyses - Deng-wei Jue; Xue-lian Sang; Zhe-xin Li; Wen-lin Zhang; Qin-hong Liao; Jianmin Tang (Food Research International, 2023)

Long-term effect of acetate and biochar addition on enrichment and activity of denitrifying anaerobic methane oxidation microbes - Jing Ding; Fan Qin; Changxin Li; Mingfang Tang (Chemosphere, 2023)

Effects of heavy metal exposure on hypertension: A machine learning modeling approach - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Chemosphere, 2023)

Comparative characterization of flavor precursors and volatiles of Taihe black-boned silky fowl and Hy-line Brown yolks using multiomics and GC-O-MS-based volatilomics - Weifang Yang; Youyou Yang; Liang Wang; Xueze Lv; Jing Li; Huanxian Cui; Chaohua Tang; Qingyu Zhao; Yaxiong Jia; Yuchang Qin; Junmin Zhang (Food Research International, 2023)

The selective activator protein-1 inhibitor T-5224 regulates the IRF4/MYC axis and exerts cooperative antimyeloma activity with bortezomib - Sishi Tang; Fangrong Zhang; Jian Li; Hang Dong; Qin Yang; Jing Liu; Yunfeng Fu (Chemico-Biological Interactions, 2023)

Comprehensively exploring the characteristics and meteorological causes of ozone pollution events in Beijing during 2013–2020 - Lei Zhang; Lili Wang; Guiqian Tang; Jinyuan Xin; Mingge Li; Xue Li; Fei Xin; Yuechang Qin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Association between co-exposure to phenols, phthalates, and polycyclic aromatic hydrocarbons with the risk of frailty - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Environmental Science and Pollution Research, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

Lipid modification to improve cryotolerance of gametes, embryos and larvae and its potential application in aquaculture species: a review - Xiaochen Zhu; Penny Miller-Ezzy; Yingying Zhao; Jianguang Qin; Youhong Tang; Yibing Liu; Xiaoxu Li (Frontiers in Marine Science, 2023)
Cryopreservation is a technique to maintain biological materials’ physiological and genetic stability at an ultralow temperature. For commercially important livestock or aquatic species, gamete and embryo cryopreservation could play a significant role in breeding programs and commercial production. For example, it could help overcome key problems such as asynchronous maturation and an unbalanced sex ratio. However, the physiochemical stresses imposed by cryopreservation can negatively affect gametes and embryos, leading to a poor survival rate. Recent studies on cryoinjury have demonstrated that the cryosensitivity of lipids is one of the key causes of cryodamage in mammalians, as lipid compositions in membranes of gametes and embryos are closely related to their cryoresistance. In addition, the cryotolerance of gametes and embryos in some mammalian species has been improved by lipid modification. However, studies on the role of lipids in the cryopreservation of gametes, embryos, and larvae are rare in fish and shellfish. Therefore, this review focuses on recent methodological advances to improve cryotolerance by lipid modification, including lipid application or manipulation in human and livestock sperm, oocytes, and embryos, and how these novel approaches could improve cryopreservation techniques in aquatic species, especially for oocytes and embryos.

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Effects of phosphatidylcholine and tocopherol during larval cryopreservation of Pacific oysters (Magallana gigas) - Xiaochen Zhu; Penny Miller-Ezzy; Mark Gluis; Yingying Zhao; Jianguang Qin; Youhong Tang; Yibing Liu; Xiaoxu Li (Aquaculture, 2023)

Multiple insights into lignin-mediated cadmium detoxification in rice (Oryza sativa) - Qin Dong; Yingjie Wu; Bing Li; Xi Chen; Lu Peng; Zulfiqar Ali Sahito; Huanxiu Li; Yulan Chen; Qi Tao; Qiang Xu; Rong Huang; Youlin Luo; et al. (Journal of Hazardous Materials, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Neonicotinoid insecticides and their metabolites: Specimens tested, analytical methods and exposure characteristics in humans - Haixin Tu; Xin Wei; Yanan Pan; Zixiong Tang; Renli Yin; Junhao Qin; Huashou Li; Adela Jing Li; Rongliang Qiu (Journal of Hazardous Materials, 2023)

Soil phosphorus drives variation in diazotrophic communities in a subtropical nitrogen-rich forest - Lingjun Qiu; Min Fan; Yunjie Li; Qin Yang; Xin Gou; Yuemei Kong; Shixing Zhou; Gang Chen; Jiulong Xie; Yuqin Chen; Li Liu; Yi Tang; et al. (Forest Ecology and Management, 2023)

Approximate analytical solution to the axisymmetric model for PVD-enhanced in-situ flushing of double-layered contaminated soils - Lianghua Jiang; Aifang Qin; Linzhong Li; Peng Tang (Computers and Geotechnics, 2023)

Tailoring hypercrosslinked ionic polymers with high ionic density for rapid conversion of CO2 into cyclic carbonates at low pressure - Xu Liao; Zeyu Wang; Zunhua Li; Lingzheng Kong; Wufei Tang; Zuodong Qin; Jinqing Lin (Chemical Engineering Journal, 2023)

The effects of a polystyrene nanoplastic on the immune response and gut microbiota of Eriocheir sinensis and its post-recovery state - Mingming Han; Chenxi Zhu; Shengkai Tang; Ji Liang; Daming Li; YanXia Guo; Zakaria Zuraini; Qin Si; Qichen Jiang (Aquatic Toxicology, 2023)

Metabolic characteristics of self-pollinated wheat seed under red and blue light during early development - Ping Zhang; Yongsheng Tang; Yongjiang Liu; Junna Liu; Qianchao Wang; Hongxin Wang; Hanxue Li; Li Li; Peng Qin (Planta, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

The regulation mechanism of hematopoiesis during ischemic and hemolytic anemia in grass carp(Ctenopharyngodon idella) - Lixiang Wei; Yanhan Bai; Rishen Liang; Junyan Lin; Minxuan Yang; Ying Tang; Hong Chen; Minshan Yao; Yao Huang; Li Lin; Zhendong Qin (Aquaculture, 2023)

Extended one generation reproductive toxicity study and effect on gut flora of genetically modified rice rich in β-carotene in wistar rats - Ying Xia; Shanshan Zuo; Yanhua Zheng; Wenxiang Yang; Xiaoqiao Tang; Xianghong Ke; Qin Zhuo; Xiaoguang Yang; Yang Li; Haiyi Liu; Bolin Fan (Reproductive Toxicology, 2023)

Extensive sea-floor oxygenation during the early Mesoproterozoic - Dongtao Xu; Zheng Qin; Xinqiang Wang; Jie Li; Xiaoying Shi; Dongjie Tang; Jingao Liu (Geochimica et Cosmochimica Acta, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Potential impact of polyethylene microplastics on the growth of water spinach (Ipomoea aquatica F.): Endophyte and rhizosphere effects - Fangming Yu; Mingyue Fu; Chijian Tang; Cuiju Mo; Songying Li; Shiyu Luo; Peiqing Qin; Yinjun Zhao; Yi Li (Chemosphere, 2023)

Experimental study on impact response of seaborne rocket launch platform - Fuzhen Pang; Yuxuan Qin; Yang Tang; Cong Gao; Haichao Li (Ocean Engineering, 2023)

Analysis of acoustic radiation characteristic of laminated paraboloidal shell based on Jacobi-Ritz-spectral BEM - Fuzhen Pang; Yang Tang; Yuxuan Qin; Jiajun Zheng; David Hui; Haichao Li (Ocean Engineering, 2023)

Enrichment strategies of heavy metals in the O/H/O process composed of biological fluidized bed for wastewater treatment: A case study of Cu and Zn - Cong Wei; Xiaoqian Cheng; Wei Sun; Xia Tang; Tuo Wei; Zijun Pang; Xiong Ke; Zhi Qin; Jiamin Pan; Gengrui Wei; Guanglei Qiu; Chunhua Feng; et al. (Journal of Cleaner Production, 2023)

Development and application of a SFC–DAD–MS/MS method to determine carotenoids and vitamin A in egg yolks from laying hens supplemented with β-carotene - Qixiang Miao; Youyou Yang; Lihong Du; Chaohua Tang; Qingyu Zhao; Fadi Li; Xiao Yao; Ying Meng; Yuchang Qin; Junmin Zhang (Food Chemistry, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

Orally administered BZL-sRNA-20 oligonucleotide targeting TLR4 effectively ameliorates acute lung injury in mice - Dandan Zhao; Yuhao Qin; Jiaqi Liu; Kegong Tang; Shuaiyao Lu; Zirui Liu; Yexuan Lin; Cong Zhang; Fengming Huang; Jiahui Chang; Chang Li; Mingyao Tian; et al. (Science China Life Sciences, 2023)

Effects of tri-n-butyl phosphate (TnBP) on neurobehavior of Caenorhabditis elegans - Jielin Tang; Jinyan Qin; Guzailinuer Kuerban; Jiayi Li; Qinyu Zhou; Hongdan Zhang; Rongli Sun; Lihong Yin; Yuepu Pu; Juan Zhang (Environmental Science and Pollution Research, 2023)

Short-term cultivation limiting soil aggregate stability and macronutrient accumulation associated with glomalin-related soil protein in Eucalyptus urophylla × Eucalyptus grandis plantations - Ye Wang; Chun He; Yutian Shi; Hui Li; Yabin Tang; Bohao Chen; Qin Ke; Lichao Wu; Lijun Chen (Science of The Total Environment, 2023)

Rainstorm sediment events in heterogeneous karst small watersheds: Process characteristics, prediction modeling and management enlightenment - Jun Jing; Jiang Yuan; Rui Li; Zaike Gu; Li Qin; Jiayong Gao; Linlv Xiao; Zhenyi Tang; Ling Xiong (Science of The Total Environment, 2023)

Construction of graphene quantum dots ratiometric fluorescent probe by intermolecular electron transfer effect for intelligent and real-time visual detection of ofloxacin and its L-isomer in daily drink - Changxing Wang; Feifei Qin; Siyuan Tang; Xiameng Li; Tingting Li; Guoqiang Guo; Chenjie Gu; Xu Wang; Da Chen (Food Chemistry, 2023)

A portable holey carbon nitride/3D Ag facilely self-assembled on copper sheet for dramatically enhanced SERS and photocatalytic performance - Lixia Qin; Min Tang; Hui Shen; Man Luo; Jian-Wei Tao; Taiyang Zhang; Shi-Zhao Kang; Xiangqing Li (Chemical Engineering Journal, 2023)

The effects of serotonergic psychedelics in synaptic and intrinsic properties of neurons in layer II/III of the orbitofrontal cortex - Zi-Hang Tang; Zhi-Peng Yu; Qiong Li; Xiao-Qin Zhang; Kadeliya Muhetaer; Zheng-Chun Wang; Peng Xu; Hao-Wei Shen (Psychopharmacology, 2023)

Interleukin-16 genetic polymorphisms in Guangxi Chinese with hepatitis B virus-related liver cirrhosis - Xiaolian Zhang; Wenjun Tang; Xue Qin; Shan Li; Dong Liang (Molecular Biology Reports, 2023)

RETRACTED ARTICLE: Comparison of preoperative ultrasound and MRI in the diagnosis of microvascular invasion in hepatocellular carcinoma - Yunmin Long; Zheng Lv; Shaoyi Wang; Bing Tang; Qin Li; Wei Zhang (Functional & Integrative Genomics, 2023)

Identification of predictors for neurological outcome after cardiac arrest in peripheral blood mononuclear cells through integrated bioinformatics analysis and machine learning - Zhonghao Li; Ying Qin; Xiaoyu Liu; Jie Chen; Aling Tang; Shengtao Yan; Guoqiang Zhang (Functional & Integrative Genomics, 2023)
Neurological prognostication after cardiac arrest (CA) is important to avoid pursuing futile treatments for poor outcome and inappropriate withdrawal of life-sustaining treatment for good outcome. To predict neurological outcome after CA through biomarkers in peripheral blood mononuclear cells, four datasets were downloaded from the Gene Expression Omnibus database. GSE29546 and GSE74198 were used as training datasets, while GSE92696 and GSE34643 were used as verification datasets. The intersection of differentially expressed genes and hub genes from multiscale embedded gene co-expression network analysis (MEGENA) was utilized in the machine learning screening. Key genes were identified using support vector machine recursive feature elimination (SVM-RFE), least absolute shrinkage and selection operator (LASSO) logistic regression, and random forests (RF). The results were validated using receiver operating characteristic curve analysis. An mRNA-miRNA network was constructed. The distribution of immune cells was evaluated using cell-type identification by estimating relative subsets of RNA transcripts (CIBERSORT). Five biomarkers were identified as predictors for neurological outcome after CA, with an area under the curve (AUC) greater than 0.7: CASP8 and FADD-like apoptosis regulator (CFLAR), human protein kinase X (PRKX), miR-483-5p, let-7a-5p, and let-7c-5p. Interestingly, the combination of CFLAR minus PRKX showed an even higher AUC of 0.814. The mRNA-miRNA network consisted of 30 nodes and 76 edges. Statistical differences were found in immune cell distribution, including neutrophils, NK cells active, NK cells resting, T cells CD4 memory activated, T cells CD4 memory resting, T cells CD8, B cells memory, and mast cells resting between individuals with good and poor neurological outcome after CA. In conclusion, our study identified novel predictors for neurological outcome after CA. Further clinical and laboratory studies are needed to validate our findings.

Rhizospheric soil organic carbon accumulated but its molecular groups redistributed via rhizospheric soil microorganisms along multi-root Cerasus humilis plantation chronosequence at the karst rocky desertification control area - Qin Tang; Qiang Li; Lingchen Tong; Rui Wu; Jiao Xu (Environmental Science and Pollution Research, 2023)

Low-cost material combination based on PTQ10 and completely non-fused nonfullerene acceptor for high VOC organic photovoltaics - Linjiao Qin; Xianda Li; Chuanqi Dong; Jialing Zhou; Qiang Guo; Ailing Tang; Yufei Zhong; Erjun Zhou (Chemical Engineering Journal, 2023)

AaWIN1, an AP2/ERF protein, positively regulates glandular secretory trichome initiation in Artemisia annua - Chen Wang; Tiantian Chen; Yongpeng Li; Hang Liu; Wei Qin; Zhangkuanyu Wu; Bowen Peng; Xiuyun Wang; Xin Yan; Xueqing Fu; Ling Li; Kexuan Tang (Plant Science, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Effects of desert riparian vegetation roots on the riverbank retreat process in the Tarim River in China - Quanli Zong; Tiegang Zheng; Ruize Tang; Kai Jin; Lin Li; Peng Qin; Chunxia Liu (Journal of Hydrology, 2023)

Evaluation of physicochemical properties, bacterial community, and product fertility during rice straw composting supplemented with different nitrogen-rich wastes - Shi-Peng Wang; Xiao-Xing Li; Zhao-Yong Sun; Wen-Liang Shuai; Zi-Yuan Xia; Cai-Yun Xie; Min Gou; Yue-Qin Tang (Bioresource Technology, 2023)

Enhancing ethylene glycol and ferric chloride pretreatment of rice straw by low-pressure carbon dioxide to improve enzymatic saccharification - Song Tang; Yan-ling Yu; Rukuan Liu; Shenghua Wei; Qin Zhang; Jie Zhao; Song Li; Qian Dong; Yan-bin Li; Yuanli Wang (Bioresource Technology, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Impact of miR-200b and miR-495 variants on the risk of large-artery atherosclerosis stroke - Shanmei Qin; Chong Shen; Wuzhuang Tang; Mengmeng Wang; Ying Lin; Zhaojun Wang; Yunzi Li; Zhizhong Zhang; Xinfeng Liu (Metabolic Brain Disease, 2023)

Stepwise solid phase extraction integrated with chemical derivatization for all-in-one injection LC-MS/MS analysis of metabolome and lipidome - Jie Chen; Pei Zhang; Siyuan Qin; Bei Tan; Siqi Li; Shaoran Tang; Chuyao Liao; Ying Zhang; Zunjian Zhang; Fengguo Xu (Analytica Chimica Acta, 2023)

Galanin, a central appetite factor, affects appetite signals in the hypothalamus and promotes feeding in Siberian sturgeon (Acipenser baerii Brandt) - Xin Zhang; Shuhuang Chen; Hongwei Wu; Zhengzhi Tian; Ni Tang; Youlian Liu; Peng Tang; Qiang Hu; Yingzi Li; Qin Kang; Defang Chen; Zhiqiong Li (Aquaculture, 2023)

Abundant bacteria and fungi attached to airborne particulates in vegetable plastic greenhouses - Changliang Nie; Xueyun Geng; Huiling Ouyang; Lina Wang; Zongzhen Li; Mingyu Wang; Xiaomin Sun; Yan Wu; Yunhan Qin; Youxin Xu; Xu Tang; Jianmin Chen (Science of The Total Environment, 2023)

Meeting China’s electricity demand with renewable energy over Tibetan Plateau - Wenjun Tang; Shan Xu; Xu Zhou; Kun Yang; Yang Wang; Jun Qin; Haikun Wang; Xin Li (Science Bulletin, 2023)

Widely targeted metabolomics analysis reveals the effect of exogenous auxin on postharvest resistance to Botrytis cinerea in kiwifruit (Actinidia chinensis L.) - Zhe-Xin Li; Shuai Yang; Xu Wang; Qin-Hong Liao; Wen-Lin Zhang; Jing Liu; Guo-Hua Liu; Jian-Min Tang (Postharvest Biology and Technology, 2023)

High-adhesion PDMS/Ag conductive composites for flexible hybrid integration - Miao Tang; Zhuo Jiang; Zekai Wang; Yajie Qin; Yizhou Jiang; Limin Wu; Zhuo Li (Chemical Engineering Journal, 2023)

Genistein attenuates neuroinflammation and oxidative stress and improves cognitive impairment in a rat model of sepsis-associated encephalopathy: potential role of the Nrf2 signaling pathway - Buyun Shi; Ming Chen; Zhi Xia; Wen Tang; Yong Li; Chenguang Qin; Amir Ahmadi; Chengjiao Huang; Hui Xu (Metabolic Brain Disease, 2023)

Spectrum and mortality of opportunistic infections among HIV/AIDS patients in southwestern China - Sirun Meng; Qiao Tang; Zhiman Xie; Nianning Wu; Yingmei Qin; Rongfeng Chen; Xiaoyu Chen; Xiu Chen; Yueqi Li; Minjuan Shi; Li Ye; Hao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
We describe the opportunistic infections (OIs) of HIV/AIDS to understand the spectrum, mortality, and frequency of multiple coinfected OIs among HIV/AIDS patients in southern China, where OIs are severe. We carried out a retrospective cohort study of hospitalized HIV-infected individuals at the Fourth People’s Hospital of Nanning, Guangxi, China, from Jan. 2011 to May. 2019. The chi-square test was used to analyze cross-infection; the Kaplan‒Meier analysis was used to compare mortality. A total of 12,612 HIV-infected patients were admitted to this cohort study. Among them, 8982 (71.2%) developed one or more OIs. The overall in-hospital mortality rate was 9.0%. Among the patients, 35.6% coinfected one OI, and 64.4% coinfected more than two OIs simultaneously. Almost half of the patients (60.6%) had CD4 + T-cell counts < 200 cells/μL. Pneumonia (39.8%), tuberculosis (35.3%), and candidiasis (28.8%) were the most common OIs. Coinfected cryptococcal meningitis and dermatitis are the most common combined OIs. The rate of anaemia (17.0%) was highest among those common HIV-associated complications. Multiple OIs are commonly found in hospitalized HIV/AIDS patients in southwestern China, which highlights the need for improved diagnosis and treatment.

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Diversity of endophytic fungi in Coptis chinensis Franch. and their activity against methicillin-resistant Staphylococcus aureus - Qianliang Ming; Xiuning Huang; Linming Guo; Dong Liu; Lingyue Qin; Yimo He; Yu Tang; Yanxia Liu; Junkang Liu; Peng Li (Folia Microbiologica, 2022)

Comprehensive multi-omics analysis of the m7G in pan-cancer from the perspective of predictive, preventive, and personalized medicine - Xiaoliang Huang; Zuyuan Chen; Xiaoyun Xiang; Yanling Liu; Xingqing Long; Kezhen Li; Mingjian Qin; Chenyan Long; Xianwei Mo; Weizhong Tang; Jungang Liu (EPMA Journal, 2022)

Protective Effect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2022)

A urinary proteomic landscape of COVID-19 progression identifies signaling pathways and therapeutic options - Yuntao Liu; Lan Song; Nairen Zheng; Jinwen Shi; Hongxing Wu; Xing Yang; Nianci Xue; Xing Chen; Yimin Li; Changqing Sun; Cha Chen; Lijuan Tang; et al. (Science China Life Sciences, 2022)

Calcification of planktonic foraminifer Neogloboquadrina pachyderma (sinistral) controlled by seawater temperature rather than ocean acidification in the Antarctic Zone of modern Sothern Ocean - Qianwei Song; Bingbin Qin; Zheng Tang; Yanguang Liu; Zhihua Chen; Jingteng Guo; Zhifang Xiong; Tiegang Li (Science China Earth Sciences, 2022)

Synthesis and insecticidal activity of novel 1,2,4-triazole derivatives containing trifluoroacetyl moieties - Fenghai Zhao; Xianjun Tang; Min Liu; Zhaohai Qin; Jia-Qi Li; Yumei Xiao (Molecular Diversity, 2022)

Effect of absolute humidity on influenza activity across different climate regions in China - Li Qi; Tian Liu; Yuan Gao; Qin Li; Wenge Tang; Dechao Tian; Kun Su; Yu Xiong; Jun Yang; Luzhao Feng; Qiyong Liu (Environmental Science and Pollution Research, 2022)

Environmental risks and the potential benefits of nanopesticides: a review - Zhenlan Xu; Tao Tang; Qin Lin; Jianzhong Yu; Changpeng Zhang; Xueping Zhao; Melanie Kah; Lingxiangyu Li (Environmental Chemistry Letters, 2022)

Effects of extreme precipitation on hospitalization risk and disease burden of schizophrenia in urban and rural Lu’an, China, from 2010 to 2019 - Yudong Wu; Zhenghai Yao; Gongyan Ma; Jian Cheng; Huabin Xu; Wei Qin; Weizhuo Yi; Rubing Pan; Qiannan Wei; Chao Tang; Xiangguo Liu; Yangyang He; et al. (Environmental Science and Pollution Research, 2022)

Standard litterbags underestimate early-stage lower-order root decomposition rate in a subtropical forest, China - Guan-tao Chen; Yu-qin Chen; Yong Peng; Hong-ling Hu; Jiu-long Xie; Gang Chen; Yin-long Xiao; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2021)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

The Regulatory Relationships Between the Gonad-Inhibiting Hormone and Insulin-Like Androgenic Gland Hormone-Binding Protein Genes in the Eyestalk-Androgenic Gland-Testis Axis of Macrobrachium rosenbergii - Meizhen Tang; Zhijie Lu; Sarath V Babu; Guang Yang; Yanan Li; Zizheng Xu; Gan Pan; Zhendong Qin; Li Lin (Frontiers in Marine Science, 2021)
Gonad-inhibiting hormone (GIH) belongs to a family of neuropeptides that are released from the eyestalks of male crustaceans and plays key roles in gonadal maturity, reproduction, and molting. However, the detailed mechanisms underlying the effects of GIH on sexual regulation have yet to be elucidated. In the present study, we aimed to demonstrate how GIH mediate the activity of the androgenic gland (AG) to affect sexual regulation. To do this, we cloned and characterized a GIH sequence from Macrobrachium rosenbergii ( Mr GIH). The open reading frame (ORF) of Mr GIH was 360 bp and codes for a polypeptide of 119 amino acids and a putative protein of 13.56 KDa. Tissue analysis showed that Mr GIH is widely expressed in a range of tissues but particularly, the eyestalk, intestine, and nerve cord. Following the ds RNA silencing of Mr GIH for 24 h, the expression levels of Mr GIH were down-regulated in both the eyestalk and AG when compared with the negative control, but significantly increased the expression of Macrobrachium rosenbergii insulin-like androgenic gland hormone-binding protein ( Mr IAGBP) in AG, thus suggesting that Mr GIH is an inhibitory factor for Mr IAGBP. In addition, we found that eyestalk removal on certain days led to increased expression levels of Mr IAGBP expression. The expression levels of Mr IAGBP peaked at 2 d in the AG after unilateral and bilateral eyestalk ablation, exhibiting a 7.27- and 6.03-fold increase, respectively. Afterward, the expression of GIH protein levels were down-regulated and IAGBP protein levels were up-regulated after GIH silencing using immunohistochemistry method, combined with the increase of IAGBP protein levels after eyestalk ablation, confirming that Mr GIH is an inhibitory factor that can moderately regulate AG development and IAGBP expression. Collectively, our findings enriched the mechanisms that control the sexual regulation pathway of male M. rosenbergii , and provided significant information for further explorations of the mechanism underlying sex regulation in other decapod crustaceans.

Humoral immune durability of IgG for anti-SARS-CoV-2 in the normal pregnant women in Wuhan, China - Hongwen Ma; Jing Peng; Ruobing Li; Xuan Zheng; Shiyao Wu; Heng Yin; Min Li; Liu Qin; Fei Tang; Yun Zhao (Immunologic Research, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Identification, expression and enzyme activity of the group III sPLA 2 s in Cyprinus carpio L - Yuxin Xu; Hongxia Li; Dihui Xu; Jianlin Li; Fan Yu; Meiyao Wang; Qin Wang; Yunsheng Wu; Qiyuan Zhang; Yongkai Tang; Juhua Yu (Journal of Fish Biology, 2021)
Five group III secreted phospholipase (pla2g3s) homologous genes located on different linkage groups were identified from common carp ( Cyprinus carpio ), which we named Ccpla2g3a1 , Ccpla2g3a2 , Ccpla2g3b , Ccpla2g3c1 and Ccpla2g3c2 . The five genes encode 530, 525, 461, 752 and 753 amino acids, respectively. Sequence analysis showed that the Ccpla2g3a s contain seven exons and the others contain four exons. Synteny analysis of fish pla2g3s indicated that pla2g3a and pla2g3b were from the same ancestor gene, and Ccpla2g3a 1, Ccpla2g3a 2, Ccpla2g3c 1 and Ccpla2g3c 2 were from the specific genome duplication of common carp. Due to the significant variation of the pla2g3bs from common carp and zebrafish ( Danio rerio ), they formed a separate group in the phylogenetic tree. The tissue distributions of Ccpla2g3 s coincided with their expression profiles during the embryo stages. The expression levels of Ccpla2g3a s and Ccpla2g3c s were low at the embryo stages, and they were abundant in the liver and brain, respectively, whereas the expression of Ccpla2g3b was high at 0.5 h after fertilization and in the ovary. We obtained three soluble recombinant proteins of the bee venom‐like PLA2 (BVLP) from Ccpla2g3 and evaluated their PLA 2 enzyme properties. The optimum pHs of MBP‐a1‐BVLP, MBP‐b‐BVLP and MBP‐c1‐BVLP were 7.5, 7.0 and 8.0, respectively, and specific activities were 7.68 ± 0.66, 4.155 ± 0.158 and 1.93 ± 0.05 U μmol –1 , respectively. The K d for Ca 2+ of MBP‐b‐BVLP was the lowest (2.6 μM), whereas the values for both MBP‐a1‐BVLP and MBP‐c1‐BVLP were about 15 μM. The K m values of three proteins ranged from 31.9 to 41.91 μM.

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

Genetic parameters for growth and Quambalaria shoot blight resistance in Corymbia citriodora subsp. variegata - Shengkan Chen; Jianbo Chen; Guanming Yi; Mei Qin; Shiqi Ren; Ziyu Deng; Qinglan Tang; Dongqiang Guo; Yuanli Zhu; Zhangqi Yang; Chonglu Zhong; Siming Gan; et al. (Euphytica, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Identification of QTL for leaf angle at canopy-wide levels in maize - Dengguo Tang; Zhengjie Chen; Jixing Ni; Qin Jiang; Peng Li; Le Wang; Jinhong Zhou; Chenyang Li; Jian Liu (Euphytica, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

Ferrous iron-induced increases in capitate glandular trichome density and upregulation of CbHO-1 contributes to increases in blinin content in Conyza blinii - Tianrun Zheng; Maojia Wang; Junyi Zhan; Wenjun Sun; Qin Yang; Zhiyi Lin; Tongliang Bu; Zizhong Tang; Chenglei Li; Jun Yan; Zhi Shan; Hui Chen (Planta, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

The association between IL18, FOXP3 and IL13 genes polymorphisms and risk of allergic rhinitis: a meta-analysis - Liang Tang; Yongjun Chen; Qin Xiang; Ju Xiang; Yonghong Tang; Jianming Li (Inflammation Research, 2020)

Tuberculosis vaccine development: from classic to clinical candidates - Junli Li; Aihua Zhao; Jun Tang; Guozhi Wang; Yanan Shi; Lingjun Zhan; Chuan Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A statistical method to construct wind speed at turbine height for study of wind power in China - X. Zhou; J. Qin; H. D. Li; W. Tang; X. Pan; B. Huang; X. Li (Theoretical and Applied Climatology, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

Cytotoxic components from the Xisha sponge Fascaplysinopsis reticulata - Guo-Fei Qin; Xu-Li Tang; Nicole J. de Voogd; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2020)

Influence of humic acid and its different molecular weight fractions on sedimentation of nanoscale zero-valent iron - Yanan Wu; Haoran Dong; Lin Tang; Long Li; Yaoyao Wang; Qin Ning; Bin Wang; Guangming Zeng (Environmental Science and Pollution Research, 2020)

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

AoStuA, an APSES transcription factor, regulates the conidiation, trap formation, stress resistance and pathogenicity of the nematode‐trapping fungus Arthrobotrys oligospora - Meihua Xie; Yunchuan Wang; Liyan Tang; Le Yang; Duanxu Zhou; Qing Li; Xuemei Niu; Ke‐Qin Zhang; Jinkui Yang (Environmental Microbiology, 2019)
Summary The APSES protein family comprises a conserved class of fungus‐specific transcriptional regulators. Some members have been identified in partial ascomycetes. In this study, the APSES protein StuA (AoStuA) of the nematode‐trapping fungus Arthrobotrys oligospora was characterized. Compared with the wild‐type (WT) strain, three Δ AoStuA mutants grew relatively slowly, displayed a 96% reduction in sporulation capacity and a delay in conidial germination. The reduced sporulation capacity correlated with transcriptional repression of several sporulation‐related genes. The mutants were also more sensitive to chemical stressors than the WT strain. Importantly, the mutants were unable to produce mycelial traps for nematode predation. Moreover, peroxisomes and Woronin bod ies were abundant in the WT cells but hardly found in the cells of those mutants. The lack of such organelles correlated with transcriptional repression of some genes involved in the biogenesis of peroxisomes and Woronin bod ies. The transcript levels of several genes involved in the cAMP/PKA signalling pathway were also significantly reduced in the mutants versus the WT strain, implicating a regulatory role of AoStuA in the transcription of genes involved in the cAMP/PKA signalling pathway that regulates an array of cellular processes and events. In particular, AoStuA is indispensable for A . oligospora trap formation and virulence.

Trend analysis of effective precipitation in different growth stages of winter wheat in Huaihe River Plain - Hanjiang Nie; Tianling Qin; Chuanzhe Li; Yang Tang; Baisha Weng; Yang Wang (Theoretical and Applied Climatology, 2019)

Stress associated protein 1 regulates the development of glandular trichomes in Artemisia annua - Yuting Wang; Xueqing Fu; Lihui Xie; Wei Qin; Ling Li; Xiaofen Sun; Shihai Xing; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

A pathogenesis-related protein 10 gene PnPR10–3 was involved in molecular interaction between Panax notoginseng and Fusarium solani - Bifeng Tang; Xin Li; Limei Pu; Qin Zhao; Xiuming Cui; Feng Ge; Diqiu Liu (Australasian Plant Pathology, 2019)

Clinical and molecular characteristics of thirty NF1 variants in Chinese patients with neurofibromatosis type 1 - Wen Wang; Weibing Qin; Hongsong Ge; Xiangsheng Kong; Chao Xie; Yunge Tang; Ming Li (Molecular Biology Reports, 2019)

Hybrids of oxoisoaporphine–tetrahydroisoquinoline: novel multi-target inhibitors of inflammation and amyloid-β aggregation in Alzheimer’s disease - Yusi Chen; Chunlin Su; Li Wang; Jingfang Qin; Shenqi Wei; Huang Tang (Molecular Diversity, 2019)

Selenium alleviates cadmium-induced inflammation and meat quality degradation via antioxidant and anti-inflammation in chicken breast muscles - Kou-Kou Tang; Hui-Qin Li; Kui-Chao Qu; Rui-Feng Fan (Environmental Science and Pollution Research, 2019)

MicroRNA-377-3p inhibits growth and invasion through sponging JAG1 in ovarian cancer - Liulin Tang; Bin Yang; Xiaolan Cao; Qin Li; Li Jiang; Dan Wang (Genes & Genomics, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Retinoic acid (RA) and bone morphogenetic protein 4 (BMP4) restore the germline competence of in vitro cultured chicken blastodermal cells - Xiaochuan Tang; Jun Shi; Xiaolian Qin; Ning Xiao; Rongyang Li; Hao Hu; Fengshuo Yang; Deshun Shi; Xiaoli Wang (In Vitro Cellular & Developmental Biology - Animal, 2019)

Effectiveness evaluation of natural fractures in Xujiahe Formation of Yuanba area, Sichuan basin, China - Hu Li; Hongming Tang; Qirong Qin; Qin Wang; Cheng Zhong (Arabian Journal of Geosciences, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

KIAA1199 promotes invasion and migration in non-small-cell lung cancer (NSCLC) via PI3K-Akt mediated EMT - Zhiyuan Tang; Yang Ding; Qin Shen; Caixin Zhang; Jun Li; Mohammed Nazar; Yan Wang; Xiaoyu Zhou; Jianfei Huang (Journal of Molecular Medicine, 2019)

Three new isoflavones from the Pueraria montana var. lobata (Willd.) and their bioactivities - Tinghui Cui; Shiyun Tang; Chunbo Liu; Zhenjie Li; Qin Zhu; Junheng You; Xiaoxi Si; Fengmei Zhang; Pei He; Zhihua Liu; Mingming Miao; Guangyu Yang; et al. (Natural Product Research, 2018)

Characterization of the complete chloroplast genome of a critically endangered decaploid rose species, Rosa praelucens (Rosaceae) - Hong-ying Jian; Shu-dong Zhang; Ting Zhang; Xian-qin Qiu; Hui-jun Yan; Shu-bin Li; Qi-gang Wang; Kai-xue Tang (Conservation Genetics Resources, 2018)

A 55 K SNP array-based genetic map and its utilization in QTL mapping for productive tiller number in common wheat - Jiajun Liu; Wei Luo; Nana Qin; Puyang Ding; Han Zhang; Congcong Yang; Yang Mu; Huaping Tang; Yaxi Liu; Wei Li; Qiantao Jiang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2018)

Abundance of transcripts of functional gene reflects the inverse relationship between CH4 and N2O emissions during mid-season drainage in acidic paddy soil - Hongling Qin; Yafang Tang; Jianlin Shen; Cong Wang; Chunlan Chen; Jie Yang; Yi Liu; Xiangbi Chen; Yong Li; Haijun Hou (Biology and Fertility of Soils, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Selection and validation of reference genes for reverse transcription quantitative real-time PCR (RT-qPCR) in silkworm infected with Bombyx mori bidensovirus - Zhaoyang Hu; Yanchun Deng; Xiaolong Zhang; Peipei Tang; Weijuan Sun; Guohui Li; Qian Yu; Qin Yao (Biologia, 2018)

De novo sequencing of the Freesia hybrida petal transcriptome to discover putative anthocyanin biosynthetic genes and develop EST–SSR markers - Dong-Qin Tang; Yi Sun; Xi Li; Zi Yan; Yi-Min Shi (Acta Physiologiae Plantarum, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Amendment of water quality standards in China: viewpoint on strategic considerations - Xiaoli Zhao; Hao Wang; Zhi Tang; Tianhui Zhao; Ning Qin; Huixian Li; Fengchang Wu; John P. Giesy (Environmental Science and Pollution Research, 2018)

Screening and isolating potential α-glucosidase inhibitors from Rhizoma Coptidis by ultrafiltration LC-PDA-ESI/MS combined with high-speed countercurrent chromatography and reverse-phase medium-pressure liquid chromatography - Ying Tang; Senlin Li; Sainan Li; Xiaojing Yang; Yao Qin; Chunming Liu; Yuchi Zhang (Medicinal Chemistry Research, 2017)

Rapid screening, separation, and detection of α-glucosidase inhibitors from Hedyotis diffusa by ultrafiltration–liquid chromatography tandem mass spectrometry–high-speed countercurrent chromatography - Xiaojing Yang; Lina Chen; Chunming Liu; Yao Qin; Ying Tang; Senlin Li (Medicinal Chemistry Research, 2017)

Effects of virus infection on plant growth, root development and phytohormone levels in in vitro-cultured pear plants - Jie Chen; Hui-Hui Tang; Liu Li; Shi-Jiao Qin; Guo-Ping Wang; Ni Hong (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Site-directed mutagenesis under the direction of in silico protein docking modeling reveals the active site residues of 3-ketosteroid-Δ1-dehydrogenase from Mycobacterium neoaurum - Ning Qin; Yanbing Shen; Xu Yang; Liqiu Su; Rui Tang; Wei Li; Min Wang (World Journal of Microbiology and Biotechnology, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

A new cycloartane-type triterpenoid from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Chu-Wen Li; Jian-Bo Sun; Yu Chang; Judy Yuet-Wa Chan; Simon Ming-Yuan Lee; Bao Zeng (Natural Product Research, 2017)

Subsessila turbinata gen. et. sp. nov. (Beltraniaceae), a Beltrania-like fungus from Thailand - Chuan-Gen Lin; Dong-Qin Dai; Darbhe J. Bhat; Kevin D. Hyde; Li-Zhou Tang; Chaiwat To-anun (Mycological Progress, 2017)

Monazite RW-1: a homogenous natural reference material for SIMS U–Pb and Th–Pb isotopic analysis - Xiao-Xiao Ling; Magdalena H. Huyskens; Qiu-Li Li; Qin-Zhu Yin; Ronald Werner; Yu Liu; Guo-Qiang Tang; Ya-Nan Yang; Xian-Hua Li (Mineralogy and Petrology, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

Resveratrol Pretreatment Decreases Ischemic Injury and Improves Neurological Function Via Sonic Hedgehog Signaling After Stroke in Rats - Pingping Yu; Li Wang; Fanren Tang; Li Zeng; Luling Zhou; Xiaosong Song; Wei Jia; Jixiang Chen; Qin Yang (Molecular Neurobiology, 2017)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Voriconazole combined with low-dose amphotericin B liposome for treatment of cryptococcal meningitis - Shan-Shan Li; Xin-Yue Tang; Sheng-Guo Zhang; Shun-Lan Ni; Nai-Bin Yang; Ming-Qin Lu (Infectious Diseases, 2016)

One-year clinical study of NeuroRegen scaffold implantation following scar resection in complete chronic spinal cord injury patients - Zhifeng Xiao; Fengwu Tang; Jiaguang Tang; Huilin Yang; Yannan Zhao; Bing Chen; Sufang Han; Nuo Wang; Xing Li; Shixiang Cheng; Guang Han; Changyu Zhao; et al. (Science China Life Sciences, 2016)

No elevation of serum adiponectin in OSA patients after continuous positive airway pressure treatment: a meta-analysis - Zhijun Li; Wenjuan Wu; Li Yang; Liang Gu; Tian Zhao; Tingyu Tang; Xiaoxi Zhou; Guangyue Qin (Sleep and Biological Rhythms, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Low Shear Stress Inhibited Endothelial Cell Autophagy Through TET2 Downregulation - Qin Yang; Xiaohong Li; Rongqing Li; Juan Peng; Zuo Wang; Zhisheng Jiang; Xiaoqing Tang; Zhao Peng; Yu Wang; Dangheng Wei (Annals of Biomedical Engineering, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

Copper isotopic signature of the Tiegelongnan high-sulfidation copper deposit, Tibet: implications for its origin and mineral exploration - Jilin Duan; Juxing Tang; Yubin Li; Sheng-Ao Liu; Qin Wang; Chao Yang; Yiyun Wang (Mineralium Deposita, 2016)

Genome-Scale Identification of Cell-Wall-Related Genes in Switchgrass through Comparative Genomics and Computational Analyses of Transcriptomic Data - Xin Chen; Qin Ma; Xiaolan Rao; Yuhong Tang; Yan Wang; Gaoyang Li; Chi Zhang; Xizeng Mao; Richard A. Dixon; Ying Xu (BioEnergy Research, 2016)

Opposite Sex Contact and Isolation: A Novel Depression/Anxiety Model - Liu Yang; Li-Jun Shi; Bei Tang; Qiu-Qin Han; Jin Yu; Gen-Cheng Wu; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Novel DOCK8 gene mutations lead to absence of protein expression in patients with hyper-IgE syndrome - Tao Qin; Yunfei An; Chaohong Liu; Junfeng Wu; Rongxin Dai; Dawei Liu; Xiaohui Li; Liping Jiang; Daoqi Wu; Xuemei Tang; Wenxia Song; Tao Wang; et al. (Immunologic Research, 2016)

A functional variant in miR-143 promoter contributes to prostate cancer risk - Haiyan Chu; Dongyan Zhong; Jialin Tang; Jie Li; Yao Xue; Na Tong; Chao Qin; Changjun Yin; Zhengdong Zhang; Meilin Wang (Archives of Toxicology, 2016)

EDARV370A associated facial characteristics in Uyghur population revealing further pleiotropic effects - Qianqian Peng; Jinxi Li; Jingze Tan; Yajun Yang; Manfei Zhang; Sijie Wu; Yu Liu; Juan Zhang; Pengfei Qin; Yaqun Guan; Yi Jiao; Zhaoxia Zhang; et al. (Human Genetics, 2016)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Plant-assisted rhizoremediation of decabromodiphenyl ether for e-waste recycling area soil of Taizhou, China - Yan He; Xinfeng Li; Xinquan Shen; Qin Jiang; Jian Chen; Jiachun Shi; Xianjin Tang; Jianming Xu (Environmental Science and Pollution Research, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Determination of the Proteins Encoded by BmBDV VD1-ORF4 and Their Interacting Proteins in BmBDV-Infected Midguts - Guohui Li; Qian Zhou; Zhaoyang Hu; Peng Wang; Qi Tang; Keping Chen; Qin Yao (Current Microbiology, 2015)

Paenibacillus wulumuqiensis sp. nov. and Paenibacillus dauci sp. nov., two novel species of the genus Paenibacillus - Jing Zhu; Wei Wang; Shan-Hui Li; Su-Qin Song; Yu-Qing Xie; Qi-Yong Tang; Ghenijan Osman; Yu-Hu Shi; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2015)

A modified genetic model for the Huangshandong magmatic sulfide deposit in the Central Asian Orogenic Belt, Xinjiang, western China - Ya-Jing Mao; Ke-Zhang Qin; Chusi Li; Dong-Mei Tang (Mineralium Deposita, 2015)

Gene expression pattern of insect fat body cells from in vitro challenge to cell line establishment - Huan Zhang; Qian Meng; Ping Tang; Xuan Li; Wei Zhu; Guiling Zhou; Ruihao Shu; Jihong Zhang; Qilian Qin (In Vitro Cellular & Developmental Biology - Animal, 2014)

Arthrobacter enclensis sp. nov., isolated from sediment sample - Syed G. Dastager; Liu Qin; Shan-Kun Tang; Srinivasan Krishnamurthi; Jae-Chan Lee; Wen-Jun Li (Archives of Microbiology, 2014)

Reference Gene Selection for Gene Expression Studies Using Quantitative Real-Time PCR Normalization in Atropa belladonna - Jindi Li; Min Chen; Fei Qiu; Baifu Qin; Wanhong Liu; Nengbiao Wu; Xiaozhong Lan; Qiang Wang; Zhihua Liao; Kexuan Tang (Plant Molecular Biology Reporter, 2014)

Cerebral hemodynamic characteristics of acute mountain sickness upon acute high-altitude exposure at 3,700 m in young Chinese men - Shi-Zhu Bian; Jun Jin; Qian-Ning Li; Jun Qin; Ji-Hang Zhang; Shi-Yong Yu; Jian-Fei Chen; Cai-Fa Tang; Lan Huang (European Journal of Applied Physiology, 2014)

Sources and the distribution of heavy metals in the particle size of soil polluted by gold mining upstream of Miyun Reservoir, Beijing: implications for assessing the potential risks - Qian Li; Hongbing Ji; Fei Qin; Lei Tang; Xinyue Guo; Jinguo Feng (Environmental Monitoring and Assessment, 2014)

Synergistic effects of TAL1 over-expression and PHO13 deletion on the weak acid inhibition of xylose fermentation by industrial Saccharomyces cerevisiae strain - Yun-Cheng Li; Zi-Xi Gou; Ze-Shen Liu; Yue-Qin Tang; Takashi Akamatsu; Kenji Kida (Biotechnology Letters, 2014)

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System - Fengxia Guo; Xiaohong Li; Juan Peng; Yaling Tang; Qin Yang; Lushan Liu; Zuo Wang; Zhisheng Jiang; Ming Xiao; Chuyu Ni; Ruixing Chen; Dangheng Wei; et al. (Annals of Biomedical Engineering, 2014)

The methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and tumor risk: evidence from 134 case–control studies - Min Tang; Shang-Qian Wang; Bian-Jiang Liu; Qiang Cao; Bing-Jie Li; Peng-Chao Li; Yong-Fei Li; Chao Qin; Wei Zhang (Molecular Biology Reports, 2014)

Berberine regulates the expression of E-prostanoid receptors in diabetic rats with nephropathy - Li Qin Tang; Sheng Liu; Shan Tang Zhang; Ling Na Zhu; Feng Ling Wang (Molecular Biology Reports, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Association between statin use and colorectal cancer risk: a meta-analysis of 42 studies - Yanqiong Liu; Weizhong Tang; Jian Wang; Li Xie; Taijie Li; Yu He; Yan Deng; Qiliu Peng; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Diverse bacteria isolated from microtherm oil-production water - Ji-Quan Sun; Lian Xu; Zhao Zhang; Yan Li; Yue-Qin Tang; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Genetic structure of rice black-streaked dwarf virus populations in China - Xiao Yin; Fang-Qiang Zheng; Wei Tang; Qin-Qin Zhu; Xiang-Dong Li; Guang-Min Zhang; Huan-Ting Liu; Bao-Shen Liu (Archives of Virology, 2013)

HBx and HBs regulate RhoC expression by upregulating transcription factor Ets-1 - Dongdong Qin; Kai Li; Jialin Qu; Sen Wang; Chengcheng Zou; Yanrui Sheng; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Berberine ameliorates renal injury by regulating G proteins-AC- cAMP signaling in diabetic rats with nephropathy - Li Qin Tang; Feng Ling Wang; Ling Na Zhu; Fei Lv; Sheng Liu; Shan Tang Zhang (Molecular Biology Reports, 2013)

Identification of Bombyx mori Bidensovirus VD1-ORF4 Reveals a Novel Protein Associated with Viral Structural Component - Guohui Li; Zhaoyang Hu; Xuli Guo; Guangtian Li; Qi Tang; Peng Wang; Keping Chen; Qin Yao (Current Microbiology, 2013)

Preparation of Novel Monoclonal Antibodies Against Chelated Cadmium Ions - Tao Kong; Xue-Qin Hao; Xiao-Bing Li; Guo-Wen Liu; Zhi-Gang Zhang; Zhi-Jun Yang; Zhe Wang; Jia Tang; Wei Yang; Jia Sun (Biological Trace Element Research, 2013)

Hepatitis B virus regulation of Raf1 promoter activity through activation of transcription factor AP-2α - Jialin Qu; Jianbo Li; Ke Chen; Dongdong Qin; Kai Li; Yanrui Sheng; Chengcheng Zou; Sen Wang; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Renoprotective effects of berberine and its possible molecular mechanisms in combination of high-fat diet and low-dose streptozotocin-induced diabetic rats - Feng Ling Wang; Li Qin Tang; Feng Yang; Ling Na Zhu; Ming Cai; Wei Wei (Molecular Biology Reports, 2013)

Bm65 is Essential for the Propagation of Bombyx mori Nucleopolyhedrovirus - Qi Tang; Guohui Li; Qin Yao; Liang Chen; Fan Feng; Yi Yuan; Keping Chen (Current Microbiology, 2013)

The connection between GRKs and various signaling pathways involved in diabetic nephropathy - Feng-Ling Wang; Li-Qin Tang; Wei Wei (Molecular Biology Reports, 2012)

Update analysis of studies on the MMP-9 −1562 C>T polymorphism and cancer risk - Li-Feng Zhang; Yuan-Yuan Mi; Qiang Cao; Wei Wang; Chao Qin; Jun-Feng Wei; Yao-Jun Zhou; Yong-Fei Li; Min Tang; Wei-Min Liu; Wei Zhang; Jian-Gang Zou (Molecular Biology Reports, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

Amycolatopsis endophytica sp. nov., a novel endophytic actinomycete isolated from oil-seed plant Jatropha curcas L. - Qian Miao; Sheng Qin; Guang-Kai Bian; Bo Yuan; Ke Xing; Yue-Ji Zhang; Qin Li; Shu-Kun Tang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

Ds-echinoside A, a new triterpene glycoside derived from sea cucumber, exhibits antimetastatic activity via the inhibition of NF-κB-dependent MMP-9 and VEGF expressions - Qin Zhao; Zhi-dong Liu; Yong Xue; Jing-feng Wang; Hui Li; Qing-juan Tang; Yu-ming Wang; Ping Dong; Chang-hu Xue (Journal of Zhejiang University-SCIENCE B, 2011)

Display of Bombyx mori Nucleopolyhedrovirus GP64 on the Bacillus subtilis Spore Coat - Guohui Li; Qi Tang; Huiqing Chen; Qin Yao; Degang Ning; Keping Chen (Current Microbiology, 2011)

Sphingomonas hunanensis sp. nov., isolated from forest soil - Qi-Hui Chen; Jin-Hua Chen; Ying Ruan; Yu-Qin Zhang; Shu-Kun Tang; Zhu-Xiang Liu; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2011)

Inhibition of Hydrogen Sulfide Generation Contributes to 1-Methy-4-Phenylpyridinium Ion-Induced Neurotoxicity - Xiao-Qing Tang; Li-Li Fan; Yu-Juan Li; Xin-Tian Shen; Yuan-Yuan Zhuan; Jian-Qin He; Jin-Hua Xu; Bi Hu; Yuan-Jian Li (Neurotoxicity Research, 2011)

Bacillus hunanensis sp. nov., a slightly halophilic bacterium isolated from non-saline forest soil - Yi-Guang Chen; Di-Fei Hao; Qi-Hui Chen; Yu-Qin Zhang; Jian-Ben Liu; Jian-Wu He; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

MnHSP90 cDNA characterization and its expression during the ovary development in oriental river prawn, Macrobrachium nipponense - Weihong Zhao; Liqiao Chen; Jianguang Qin; Ping Wu; Fengying Zhang; Erchao Li; Boping Tang (Molecular Biology Reports, 2011)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Yaniella soli sp. nov., a new actinobacterium isolated from non-saline forest soil in China - Yi-Guang Chen; Jun Chen; Qi-Hui Chen; Shu-Kun Tang; Yu-Qin Zhang; Jian-Wu He; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2010)

Characterization of an Alien Chromosome of Oryza officinalis Transferred the Genomic and Cytological Environment of Oryza sativa - Gang Li; Ming Tang; Wei Hu; Guangcun He; Hong Liu; Xuequn Liu; Rui Qin (Journal of Plant Biology, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Nocardiopsis terrae sp. nov., a halophilic actinomycete isolated from saline soil - Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Zhu-Xiang Liu; Li-Hua Xu; Li-Xin Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

KCNQ1 loss-of-function mutation impairs gastric acid secretion in mice - Qin Pan; Jun Ma; Qinshu Zhou; Jun Li; Yongqing Tang; Yi Liu; Yiqing Yang; Junjie Xiao; Luying Peng; Pengjuan Li; Dandan Liang; Hong Zhang; et al. (Molecular Biology Reports, 2010)

QSPR model for bioconcentration factors of nonpolar organic compounds using molecular electronegativity distance vector descriptors - Li-Tang Qin; Shu-Shen Liu; Hai-Ling Liu (Molecular Diversity, 2010)

Isolation and characterization of a novel cDNA encoding methyl jasmonate-responsive transcription factor TcAP2 from Taxus cuspidata - Yiling Dai; Qiulin Qin; Dalin Dai; Lisheng Kong; Wei Li; Xiaojun Zha; Yuanjie Jin; Kexuan Tang (Biotechnology Letters, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Alteromonas halophila sp. nov., a new moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Huai-Dong Xiao; Shu-Kun Tang; Yu-Qin Zhang; Entomack Borrathybay; Xiao-Long Cui; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Streptomyces serianimatus sp. nov., isolated from a rhizophere soil - Yong-Xia Wang; Xiao-Yang Zhi; Hua-Hong Chen; Yu-Qin Zhang; Shu Kun Tang; Cheng-Lin Jiang; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2007)

Overexpression ofGbERF confers alteration of ethylene-responsive gene expression and enhanced resistance toPseudomonas syringae in transgenic tobacco - Jie Qin; Kaijing Zuo; Jingya Zhao; Hua Ling; Youfang Cao; Chengxiang Qiu; Fupeng Li; Xiaofen Sun; Kexuan Tang (Journal of Biosciences, 2006)

Quantitative trait loci mapping and epistatic analysis for grain yield and yield components using molecular markers with an elite maize hybrid - Jian-bing Yan; Hua Tang; Yi-qin Huang; Yong-lian Zheng; Jian-sheng Li (Euphytica, 2006)

Development of a Latex Agglutination Test Using The Major Epitope Domain of Glycoprotein E of Pseudorabies Virus Expressed in E. coli to Differentiate Between Immune Responses in Pigs Naturally Infected or Vaccinated with Pseudorabies Virus - Tang Yong; Chen Huan-chun; Xiao Shao-bo; Qin Ya-li; He Qi-gai; Ren Yu-qi (Veterinary Research Communications, 2005)